An efficient lightweight XHP-CNN with multi-task adaptation for mango leaf disease recognition on mobile edge devices - Yi-Chen Chen; Jen-Cheng Wang; Mu-Hwa Lee; Yin-Hao Lai; Joe-Air Jiang (Computers and Electronics in Agriculture, 2026)

Coupled evolution of marine chemocline and nitrogen cycling on continental margins during the Middle Ordovician cooling - Chaogang Fang; Bolin Zhang; Mu Liu; Min Zeng; Haibo Huang; Chengcheng Zhang; Long Teng; Xiangli Wang; Guang-Yi Wei (Global and Planetary Change, 2026)

Characteristics and priority control species of ambient VOCs in a coal-coking industrial park in the Fenwei Plain - Yifei Chen; Yi Ning; Jing Ma; Fengxian Liu; Ling Mu; Siyu Liang; Huili Jin; Qian Zhang; Yijie Bi (Environmental Pollution, 2026)

Deciphering mechanisms of environmental adaptation, antibiotic tolerance, and potential virulence traits of Pseudomonas baetica isolated from anthropogenic habitat - Mu-Qi Zhang; Yi-Cheng Wang; Ming-Ying Mao; Yin-Qiu Qin; Peng Yan; Hui-Min Fu; Yuan-Xiang Mao; Ji-Cheng Liu; You-Peng Chen; Meng-Jiao Gao (Journal of Environmental Chemical Engineering, 2026)

Insight into impacts of protease specificity on bitterness, digestibility, and peptidomic profiles of demineralized sweet whey exposed prior to limited hydrolysis - Jiayu Deng; Zhishen Mu; Qiang Huang; Xianing Che; Yi Xue; Zhanmei Jiang; Yun Chen (International Dairy Journal, 2026)

Enhancing composite emulsion stability through electrostatic modulation of polysaccharides-whey protein isolate interactions for probiotic encapsulation - Wei-Gang Xin; Yu-Hang Jiang; Yu-Han Dong; Yu-Hang Hou; Mu-Ying Du; Amel Ahmed Ibrahim; Zsolt Zalán; Hua-Yi Suo (Food Chemistry, 2026)

Elucidating the storage destabilization behavior of casein micelle models under direct-steam-infusion UHT processing: insights from plasmin hydrolysis patterns revealed by peptidomics - Mengyuan Guo; Yi Wang; Pengjie Wang; Zhishen Mu; Wentao Qian; Xiaojun Wei; Fazheng Ren; Jie Luo (Food Chemistry, 2026)

Extraction optimization, purification, and structural characterization of Yacon polysaccharide: An inhibitor against α-glucosidase/α-amylase - Zhen-Zhou Li; Zhe-Xuan Mu; Shao-Feng Li; Yi-Han Ding; Shadrack Vundi Benjamin; Ruo-Jia Zhu; Xiang-Yu Wang; Zhen-Yu Wang; Hua Zhang (Food Chemistry, 2026)

Effects of fine particle migration caused by one wetting-drying cycle on desiccation micro-cracks in intact loess - Zhi-yuan He; Peng-hui Ma; Qing-yi Mu; Chao Zhou; Ke Mu; Zhi-jie Jia; Jian-bing Peng (Engineering Geology, 2026)

Enhanced biomethane production associated with olivine-stimulated CO2 reduction in petroleum reservoir production water - Muhammad Javed; Muhammad Irfan; Le-Gang Chen; Bo Fang; Bo-Wen Wang; Ghulam Dastgir; Muhammad Kashif Javed; Lei Zhou; Yi-Fan Liu; Shi-Zhong Yang; Ji-Dong Gu; Bo-Zhong Mu (Bioresource Technology, 2026)

Protein glutaminase–mediated deamidation improves the hydration properties of spray-dried micellar casein powders by coupling hierarchical porosity with surface charge and hydrophobicity modulation - Yi-Fang Gao; Stella Zhu; Di Su; Ying-Hua Zhang; Zhi-Shen Mu (Food Chemistry, 2026)

A synergistic antifungal buccal composite integrating Aureobasidin A and alkaline modulation for localized treatment of oral candidiasis - Jiaxin Yi; Li Xie; Xueping Shui; Xinzhi Tan; Yandong Mu; Wei Fei; Li Xiao; Weidong Tian; Jun Guo (Chemical Engineering Journal, 2026)

Investigation, Evaluation and Geoconservation of the Yardang Landforms in Dahaidao Region, Hami Basin, Xinjiang, NW China - Qing-Wei Song; Hong-Xu Mu; Zhao-Jie Chen; Xu-Dong Song; Xiu-Long Zhang; Ying Dong; Yi-En Xiao (Geoheritage, 2026)

Water droplets in crude oil: A new window into microbiome and microbial activity in subsurface oil reservoirs - Qiao-Hui Wang; Yi-Fan Liu; Lei Zhou; Shi-Zhong Yang; Ji-Dong Gu; Bo-Zhong Mu (International Biodeterioration & Biodegradation, 2026)

Laser-processed biomimetic hydrogel patches with tunable bio-adhesion, muscle tissue regeneration, and synergistic antibacterial activity - Luxing Wei; Jun Huang; Yingwen Mu; Liuguang Song; Yi Yu; Yuquan Wang; Gexing Peng; Ningji Gong; Jian Shen (Chemical Engineering Journal, 2026)

A genetic clash of sister groups: first-ever intergeneric and interspecific mitogenome comparisons between two close gall midge genera (Cecidomyiidae: Cecidomyiinae: Cecidomyiini): the floral and veggie-versatile Contarinia and the mango-mad Procontarinia, with phylogenetic applications - Xiu-Fang Dong; Yi-Fan Zhang; Xu-Yuan Gao; Ning-Bo Ma; Yu Ji; Yan-Fei Li; Yi-Ran Mu; Zheng-Hao Yue; De-Wei Wei; Yong-Hao Yu; Hai-Li Qiao; Wen-Jun Bu; et al. (Arthropod-Plant Interactions, 2026)

OS-SBDA: a dual-track Schrödinger Bridge adversarial framework for unpaired optical-to-SAR image translation - Wenjun Zhu; Jiangfu Xu; Xiangli Nie; Zihao Gao; Yang Yi; Yimin Mu; Mengyi Zhang (International Journal of Remote Sensing, 2026)

Tetramethylpyrazine promotes spinal cord injury repair by modulating macrophage M1/M2 polarization via inhibition of the IL-6/JAK2/STAT3 pathway - Huizhong Bai; Luyao Huo; Ruiqin Yu; Bowen Deng; Jiashu Yue; Yu Jiang; Yimin Zhou; Yi Zhao; Xiaohong Mu (Toxicology and Applied Pharmacology, 2026)

Axial compressive behavior of seawater sea-sand concrete filled double-skin aluminum tubular columns: A fundamental study for marine structures - Yan-jun Chang; Mu-yang Li; Yi-jie Zong; Li-li Jin (Ocean Engineering, 2026)

Sulfur vacancy-rich MoS2 nanoflowers as electron shuttles boost Fe(VI) activation for efficient micropollutant degradation - Lian Wu; Xin Zhou; Zi-Yi Han; Hui-Zhi Mu; Lu Wang; Yu-Lei Liu; Jun Ma (Journal of Hazardous Materials, 2026)

Reliability enhancement of PVDF-HFP modified perovskite solar cells under synergistic space-relevant stress conditions - Harini Srikanth Rao; Seoungjun Ahn; Wei-Hao Chiu; Wei-Chen Chu; Yi-Wen Sung; Gao Chen; Kun-Mu Lee (Chemical Engineering Journal, 2026)

Intraguild predation risks revealed by functional responses: laboratory evaluation of three spider species preying on the generalist predatory Arma custos (Hemiptera: Pentatomidae) - Yin-Lin Mu; Jun-Yi Gao; Lin Yang; Mao-Xian Wang; Xiang-Sheng Chen (Phytoparasitica, 2026)

Sustainable stabilisation of collapsible loess with quicklime-recycled GGBS mixtures - Bao-Lin Dai; Chao Zhou; Qing-Yi Mu; Jian-Bing Peng (Geomechanics for Energy and the Environment, 2026)

Predictive Multi-Physics coupling coal combustion model under rapid heating - Hanjian Li; Ying Zhao; Shichen Ding; Xiaoxuan Lyu; Yi Wang; Sheng Su; Song Hu; Jun Xiang; Qingsong Mu; Yanfei Li; Xian Fan; Huanying Chi (Fuel, 2026)

LC-HRMS profiling of processing-induced formation of carcinogenic N-nitrosamines in Areca nut products - Yuan-Jhe Chang; Hsueh-Ju Lu; Yet-Ran Chen; Yi-Jhen Wang; Rajendra Bose Muthukumaran; Chiung-Wen Hu; Mu-Rong Chao (Food Chemistry, 2026)

Integration of AHRR methylation, heavy metals, and clinical characteristics for urothelial carcinoma risk stratification: An explainable artificial intelligence approach - Chia-Min Chung; Chao-Hsiang Chang; Chin-Huai Chang; Wen-Chi Chang; Yi-Huei Chang; Po-Jen Hsiao; Chi-Shun Lien; Han Chang; Mu-Chi Chung; Chi-Jung Chung (Environmental Pollution, 2026)

PM2.5 exposure and breast cancer risk: Independent and combined effects of ESR1 rs2046210 and FGFR2 rs2981582 in a Taiwanese cohort - Yi-Ching Liaw; Chih-Da Wu; Yi-Chia Liaw; Shu-Yi Hsu; Mu-Rong Chao; Chiung-Wen Hu; Yung-Po Liaw (Environmental Pollution, 2026)

A potent human neutralizing antibody targeting the receptor-binding site in the glycoprotein gp350 of Epstein-Barr virus - Qingtai Liang; Qian-Ying Zhu; Xin-Yan Fang; Jing Wei; Yi-En Xu; Yanan Zuo; Guo-Long Bu; Chu Xie; Sisi Shan; Cong Sun; Zheng Liu; Linqi Zhang; et al. (Science China Life Sciences, 2026)

Integrating Biotic and Abiotic Measures Enhances Early Ecosystem Functionality in Degraded Grasslands - Yang Lei; Chang-Ning Li; Tuo Yao; Yakov Kuzyakov; Chen Zhang; Shan-Mu He; Jia-Li Chai; Jie Bai; Yi-Xin Zhang; Shuang-Xiong Li (Journal of Soil Science and Plant Nutrition, 2026)

Cold Stress and Molecular Adaptations in Aquatic Organisms: A Comparative Review of Fish, Crustaceans, and Mollusks - Lan Li; Yihong Mu; Chunrong Zuo; Minfang Zhao; Zhiqiu Huang; Wenli Zhang; Meihong Qiu; Yi Huang (Fishes, 2026)
Cold stress poses a significant challenge to aquatic organisms, affecting their survival, growth, and metabolic processes. This review explores the molecular mechanisms by which fish, crustaceans, and mollusks respond to cold stress, highlighting the shared and species-specific pathways that facilitate adaptation. Common responses to cold stress include modulation of energy metabolism, regulation of oxidative stress, immune responses, and maintenance of proteostasis. In particular, the activation of the adenosine 5′-monophosphate-activated protein kinase (AMPK) and mechanistic target of rapamycin (mTOR) pathways plays a critical role in regulating energy balance and autophagy in response to low temperatures. Furthermore, we examine the specific adaptive mechanisms employed by different groups of aquatic organisms. Fish utilize pathways such as peroxisome proliferator-activated receptor alpha/peroxisome proliferator-activated receptor gamma coactivator 1-alpha (PPAR/PGC-1α) and fatty acid oxidation to optimize energy utilization and improve cold tolerance. Crustaceans rely on crustacean hyperglycemic hormone (CHH) signaling and AMPK pathway activation, while mollusks employ metabolic suppression and glycogen storage to survive cold exposure. Moreover, the regulation of autophagy and apoptosis, mediated by p53 and cyclin-dependent kinase 1 (Cdk1), ensures the survival of healthy cells under prolonged cold stress, with autophagy maintaining energy homeostasis and apoptosis eliminating damaged cells. This review also discusses the role of molecular chaperones like heat shock protein 70 (HSP70) and the ubiquitin-proteasome system (UPS) in protein homeostasis, highlighting their importance to protect cells under cold stress. The combined action of these molecular pathways allows aquatic organisms to cope with and adapt to cold environments, ensuring cellular integrity and enhancing survival. Future research should focus on integrating molecular, physiological, and ecological approaches to better understand cold tolerance mechanisms and improve aquaculture practices under climate change scenarios.

Compressive sensing based seismic data acquisition a case study in northeast China - Jian-guo Chen; Guo-xu Shu; Sheng-qiang Mu; Yi-yuan Wang; Shou-dong Huo (Applied Geophysics, 2026)

Two undescribed benzofuran derivatives from chaetomium elatum - Chen-Yi Yan; Feng Ju; Yu-Hui Chen; Yu-Ting Mu; Yun-Jie Hu; Da-Le Guo; Yun Deng; Qi-Xuan Kuang (Natural Product Research, 2026)

Corrigendum to ‘ORF603 derived from AcMNPV plays entirely opposite roles in regulating BmNPV infection’ [Pesticide Biochemistry and Physiology 220 (2026) 107056] - Xin-yi Ding; Jiang-zhi Su; Yu-shuo Song; Wen-Jing Yu; Zuo-min Shao; Sheng Qin; Xia Sun; Xue-yang Wang; Xiao-mei Ma; Mu-wang Li (Pesticide Biochemistry and Physiology, 2026)

ORF603 derived from AcMNPV plays entirely opposite roles in regulating BmNPV infection - Xin-yi Ding; Jiang-zhi Su; Yu-shuo Song; Wen-Jing Yu; Zuo-min Shao; Sheng Qin; Xia Sun; Xue-yang Wang; Xiao-mei Ma; Mu-wang Li (Pesticide Biochemistry and Physiology, 2026)

Gestational dibutyl phthalate exposure impairs the ovarian reserve in offspring mice through METTL14-m6A-mediated PI3K-AKT-FOXO3a activation - Yan Zhang; Fuqing Yi; Ying He; Yidan Ma; Xinyi Mu; Yanqing Geng; Xin Yin; Rufei Gao; Liping Yan; Xuemei Chen; Junlin He (Journal of Hazardous Materials, 2026)

Non-photosynthetic microorganisms drive the transformation of bioinert emerging contaminants through photoinduced singlet oxygen production - Qi Huang; Jie Huang; Xin Zhang; Mu-Cen Yao; Yan-Yun Hu; Yi Hu; Zheng-Shuang Hua; Guo-Ping Sheng (Journal of Hazardous Materials, 2026)

Synergistic metabolism between Veillonella ratti and Lactobacillus acidophilus and its inhibition of enterohemorrhagic Escherichia coli infection in piglet - Wenhui Zheng; Yi Hao; Hejing Wang; Yuxin Han; Wenchao Song; Yanan Mu; Tianjia Feng; Zhaoyu Zhang; Bianfang Liu (Archives of Microbiology, 2026)

Biological control of a novel strain Bacillus velezensis BFWR11 against tomato early blight - Yuxin Han; Wenhui Zheng; Yanan Mu; Tianjia Feng; Yi Hao; Wenchao Song; Jin Cai; Boting Zhan; Zhaoyu Zhang; Bianfang Liu (Antonie van Leeuwenhoek, 2026)

AI-driven discovery of natural product-derived FAK1 inhibitors for idiopathic pulmonary fibrosis - Xing-Yi Chen; Mei-Hong Lu; Bin Li; Ya Zhou; Li Liu; Hao Yang; Qiu-Yu Wang; Lin Chang; Yu-Lan Zhao; Dong-Mei Wang; Bin Li; Ben-Rong Mu (Molecular Diversity, 2026)

Morphological study of the mating organs and their regeneration in Portunus trituberculatus (Miers, 1876) - Yi Zhang; Jian Yang; Chunlin Wang; Changkao Mu; Congcong Hou (Journal of Oceanology and Limnology, 2026)

Germ layer specification and organotropism in lymphoma invasion - Yan Dong; Peng-Peng Xu; Xiao Han; Yu-Qing Wang; Yi Chen; Ying Fang; Yue Zhu; Qing Shi; Rong Shen; Zi-Yang Shi; Niu Qiao; Shu Cheng; et al. (Science Bulletin, 2026)

Evaluation of the effectiveness of indigenous entomopathogenic fungi for controlling chilli thrips (Scirtothrips dorsalis Hood) in blueberry under greenhouse conditions - Hsin-Yu Lin; Yi-Ju Chen; Kusum Mushyakhwo; Chin-Mu Chen; Yu-Shin Nai (BioControl, 2026)

Targeting ACSL4: A potential strategy to alleviate deoxynivalenol-mediated intestinal ferroptosis, oxidative stress, and immunosuppression in Channa argus - Yi-Ran Zhao; Tong-Hao Wang; Ze-Xin Zhao; Xiao-Tian Niu; Hong-Ming Lv; Yan-Bing Li; Yang Cao; Mu-Yang Li (Aquaculture, 2026)

Performance assessment of canopy gap fraction retrieval using multiple airborne LiDAR instrument configurations - Yi Li; Hao Tang; Shanshan Wei; Donghui Xie; Xihan Mu; Guangjian Yan (Remote Sensing of Environment, 2026)

Quantifying the impacts of increasing light and moderate rainfall on permafrost thermal regimes over the Qinghai-Tibet Plateau: A controlled sensitivity study - Guofei Zhang; Cuicui Mu; Yining Zhang; Xiaofan Zhu; Yi Zhao; Zhuotong Nan (Journal of Hydrology, 2026)

The synergistic effect of algal-bacterial granular sludge in a sequencing batch reactor with tetracycline-containing synthetic livestock and poultry breeding wastewater - Yuanda Du; Shoubo Zhao; Yanan Gao; Yujie Yan; Yi Kong; Wenwen Meng; Xinru Lu; Shun Zheng; Haolin Mu; Xiaojing Chen; Qiang Kong (Journal of Environmental Management, 2026)

Effect of CO2 and H2O on pyrolysis characteristics and structural evolution of Zhundong coal under rapid heating rate - Huanying Chi; Shichen Ding; Ying Zhao; Xiaoxuan Lyu; Yi Wang; Sheng Su; Song Hu; Jun Xiang; Qingsong Mu; Yanfei Li; Xian Fan; Hanjian Li (Fuel, 2026)

Imiquimod-induced colitis: A novel ROS/ERK-driven model of intestinal inflammation and barrier dysfunction - Kuang-Ting Liu; Shu-Hao Chang; Kuan-Chen Wu; Zheng-Yi Li; Mao-Chia Chang; Yen-Chu Huang; Mu-Chi Chung; Shih-Chung Wang; Yi-Ju Chen; Jeng-Jer Shieh (Chemico-Biological Interactions, 2026)

Sustainable photocatalytic solutions to pollution and energy challenges: Novel S-scheme heterojunction NiFe2O4/MIL-101(Cr) achieves efficient degradation of Rhodamine B and hydrogen production - Keren Shi; Xiaoyu Li; Yuren Luo; Ziyan Wang; Qiaowei Xiao; Wende Yi; Wenxin Ji; Jingyang Mu; Huiqin Yao (Fuel, 2026)

Sugarcane polyphenols modulate gut microbiota and odor-associated metabolites during in vitro fecal fermentation of elderly - Hongye Li; Yun Bian; Yi Wu; Xueqing Hang; Mengqing Zhang; Luchuan Gao; Yifei Dong; Tanhang Mu; Wei Zhao (Food Bioscience, 2026)

Potential of Spread Field Imaging Collimation Technology in SPECT to Differentiate Sub-endocardial and Sub-epicardial Regions: A Phantom Study - Yi-Hwa Liu; Richard Palyo; Divyani Goyal; Chi Liu; Zhiqiang Mu; Zhong Tao; Albert J. Sinusas; Edward J. Miller; Zhiping Mu (Journal of Medical and Biological Engineering, 2026)

Gonadal Transcriptome Analysis Identifies Sex-Related Genes and Regulatory Pathways in Spotted Longbarbel Catfish (Hemibagrus guttatus) - Kun Zhao; Yuanyuan Wang; Yexin Yang; Yi Liu; Chao Liu; Shandian Zhu; Jinhui Sun; Xidong Mu (Fishes, 2026)
Hemibagrus guttatus is a large omnivorous fish of significant economic value, listed as a Class II protected species in the National Key Protected Wildlife List in 2021 in China. To provide a theoretical foundation for the artificial breeding of H. guttatus, this study employs high-throughput transcriptome sequencing of testes and ovaries to elucidate the molecular regulatory pathways involved in sex differentiation. Because H. guttatus exhibits no obvious sexual dimorphism even during the breeding season, the distinctive contribution of this study compared with previous gonadal-transcriptomic investigations in other Siluriformes lies not only in documenting sex-biased genes but also in providing a molecular foundation for developing non-lethal sex-identification methods for this morphologically indistinguishable species. A total of 303,192,896 raw reads were obtained, with an effective data rate of 98.4%, indicating high sequencing quality. Differential expression analysis identified 8694 genes, including 6369 upregulated in testes and 2325 upregulated in ovaries. Among these, 88 genes were functionally annotated as sex-related, with 62 testis-biased genes such as spata17, sox9, and dmrt1, and 26 ovary-biased genes including cyp19a, wnt8, and sox12. KEGG pathway enrichment analysis revealed that the TGF-β signaling pathway, insulin secretion, and steroid hormone biosynthesis may play crucial roles in gonadal development and differentiation in H. guttatus. The expression patterns of key genes such as hsd11b1, amh, and insl3 were validated by quantitative real-time PCR, showing consistency with the transcriptome results. These findings lay a molecular foundation for understanding the regulatory mechanisms of sex differentiation in H. guttatus, and provide candidate genes for further investigation into the genetic basis of gonadal development, which is essential for improving artificial reproduction and selective breeding practices.

Cross-phenological domain adaptation for early-stage peach detection - Qiang Zhai; Jingsha Shi; Yi Li; Ziqi Yang; Yaolin Han; Jiong Mu (Computers and Electronics in Agriculture, 2026)

Effects of photoperiods on hypothalamic-pituitary-interrenal (HPI) axis and immune responses in high latitude fish Phoxinus lagowskii - Xiaoyu Zhao; Yiwen Liu; Weichen Wang; Yi Chang; Tingting Hu; Kai Ma; Weijie Mu (Aquaculture, 2026)

Rice SINA E3 ligases dichotomously control ERECTA1 ubiquitination and stability to regulate panicle morphogenesis and grain yield - Zi-Qi Lu; Tao Guo; Ying-Jie Cao; Jun-Xiang Shan; Wang-Wei Ye; Nai-Qian Dong; Yi Kan; Yi-Bing Yang; Shuang-Qin Guo; Jie-Jie Lei; Xiao-Rui Mu; Ji-Fu Zhou; et al. (Molecular Plant, 2026)

Mechanisms of Cr (VI) reduced by nitrogen-fixing bacteria - Zi-Xiao Xue; Han-Lin Gu; Zi-Yi Mu; Yun Niu; Meng-Die Li; Zhuo Lu; Wei Zhang (Journal of Hazardous Materials, 2026)

Unveiling the black box: Multi-omics reveal how biochar supercharges synthetic biofilms for superior bioremediation - Bo Zhang; Xiaoying Hu; Lu Han; Zhen Guo; Yongqi Liu; Huiyao Li; Yuze He; Tianyu Liu; Qingyuan Pan; Yi Mu; Jianhua Qu; Hongqi Yu; et al. (Journal of Hazardous Materials, 2026)

A double Z-scheme ternary heterojunction FeNi2S4@MoS2/g-C3N4: Interfacial synergistic mechanism of charge carrier dynamics-accelerated adsorption-photocatalysis for efficient pollutant degradation and hydrogen evolution - Keren Shi; Ziyan Wang; Qiaowei Xiao; Xiaoyu Li; Wende Yi; Wenxin Ji; Jingyang Mu; Huiqin Yao (Journal of Environmental Management, 2026)

Enrichment and cultivation of thermophilic Bathyarchaeia from oil reservoirs via systematic cultivation profiling - Qing-Ping He; Yi-Fan Liu; Bo-Wen Wang; Lei Zhou; Shi-Zhong Yang; Ji-Dong Gu; Bo-Zhong Mu (International Biodeterioration & Biodegradation, 2026)

Structural modulation of casein peptide-hydroxytyrosol self-assembled nanocomplexes: Enhanced gastrointestinal stability and in vitro antioxidant activity - Si-Yi Han; Hong-Fu Zhao; Wen-Qi Liang; Ying-Hua Zhang; Zhi-Shen Mu (Food Research International, 2026)

Bioconversion of CO2 to methane energy by Methanococcus maripaludis in newly-designed bioreactor system: Kinetic characteristics, parameter optimization and grid-quality production - Lei Zhou; Jie Gao; Le-Gang Chen; Yi-Fan Liu; Shi-Zhong Yang; Ji-Dong Gu; Bo-Zhong Mu (Bioresource Technology, 2026)

Transcriptome-wide identification of glycoRNAs by Clier-seq pipeline - Nannan Zhu; Yan-Lin Yang; Yuan-Tao Liu; Zheng-Zhou Lu; Yan Wang; Yi-Ling Luo; Ning Meng; Yan Yuan; Qian Zhong; Mu-Sheng Zeng (Science China Life Sciences, 2026)

Microscopic probing into plasmodesmata (PD) and PD-derived intercellular gateways (PdIGs): Beyond morphology - Ming-fang Lv; Wei-na Shang; Yuan-xing Dai; Jun-ying Li; Yi Li; Shuai Fu; Jian Hong; Li Xie; Heng-Mu Zhang (Protoplasma, 2026)

Long Non-Coding RNA PVT1 Inhibits Apoptosis Through the miR-30d-5p/CaMKIIδ Axis in Hypoxic–Ischemic Brain Injury - Fengyan Zhao; Junyan Liu; Zihong Xiong; Lingyi Huang; Yuanyuan Zhao; Shiping Li; Junjie Ying; Qian Liu; Shaopu Wang; Xiaojuan Su; Jun Tang; Yi Qu; et al. (Molecular Neurobiology, 2026)

Acute effects of two different combined exercise modalities on executive function and circulating neurotrophic factors in young healthy adults - Yi-Hung Liao; Toby Mündel; Ying-Chu Chen; Shiow-Chwen Tsai; Kuo-Cheng Wu; Mu-Tsung Chen; Li-Chen Lee; Chih-Peng Su; Yu-Kai Chang; Chung-Yu Chen (European Journal of Applied Physiology, 2026)

Discovery of lignans and curcuminoids as the effective inhibitors of pancreatic lipase: structure-activity relationship and inhibitory mechanism - Jie Mu; Rui-Dong Wang; Yi-Shu Zhao; Tian-Chi Lu; Si-Si Chen; Yi-Jing Wang; Hua Wei; Li-Wei Zou (Natural Product Research, 2025)

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

Simultaneous removal of nitrate and ammonia at the sulfur/pyrite-microbe interface: A novel insight of pyrite in wastewater polishing treatment for nitrogen metabolism - Jianjun Luo; Cheng Hou; Zijun Wang; Ningyuan Gui; Yi-Xuan Wang; Xinbai Jiang; Yang Mu; Jinyou Shen (Journal of Hazardous Materials, 2025)

Iron-doped biocarriers enhanced nitrogen removal from saline wastewater in an unplanted constructed wetland-microbial electrolytic cell system - Longqiang Yi; Changyuan Liu; Xinyu Rong; Kexin Li; Ruina Zhang; Xin Su; Xinting Mu; Li Wan; Yinghai Wu; Rui Han (Journal of Environmental Management, 2025)

Construction of smartphone-assisted electrochemical molecularly imprinted sensor based on magnetic MOF@COF as a novel platform for portable and sensitive detection of staphylococcal enterotoxin B - Wei Hu; Minghao Ma; Bin Du; Yikan Zhao; Jiang Wang; Bing Liu; Xihui Mu; Zhangyan Hu; Zhihao Yi; Zhaoyang Tong (Journal of Environmental Chemical Engineering, 2025)

Morphology of root systems and tensile properties of individual roots across various soil types and layer thicknesses induced by bedrock weathering - Bin-bin Guo; Qing-yi Mu; Yan-jun Shen; Anthony Kwan Leung; Jian-bing Peng (CATENA, 2025)

The critical role of mitophagy in cell senescence-mediated pulmonary fibrosis and potential therapeutic strategies - Xing-Yi Chen; Dong-Mei Wang; Ya Zhou; Li Liu; Tao Zhu; Zhao Ran; Mei-Hong Lu; Ben-Rong Mu (Molecular Biology Reports, 2025)

Multi-target surrounding control of spacecrafts with sensor faults: A quantitative prescribed performance approach with event-triggered mechanism - Jiyuan Yi; Zhongcheng Mu; Dong Ye; Sunhao Chu; Shufan Wu (Advances in Space Research, 2025)

BmeIF4E2 promotes AcMNPV infection in the silkworm, Bombyx mori, by direct interaction - Xin-Yi Ding; Jiang-Zhi Su; Wen-Jing Yu; Qian-Qian Jiao; Zuo-Min Shao; Ai-Jun Wan; Sheng Qin; Xia Sun; Xue-Yang Wang; Ding-Ding Lü; Mu-Wang Li (Pesticide Biochemistry and Physiology, 2025)

Regulation of peptide hydrophobicity by self-assembly of casein peptides with ferulic acid to potentially reduce peptide bitterness and improve in vitro digestive activity - Si-Yi Han; Hong-Fu Zhao; Bo-Kang Yu; Ying-Hua Zhang; Zhi-Shen Mu (Food Chemistry, 2025)

Effects of phenological uniformity on prediction accuracy of wheat yield and biomass - Yandong Yang; Qing Li; Qinwen Lin; Huimin Wang; Yi Shi; Gengchen Wu; Yue Mu; Dong Jiang; Seishi Ninomiya (Field Crops Research, 2025)

Entropy engineering in metavalent-bonded SnTe for high thermoelectric performance - Yaning Wang; Yi Yuan; Yonghui Ma; Guojian Li; Tie Liu; Wangzhong Mu; Qiang Wang (Chemical Engineering Journal, 2025)

2.2-billion-year-old KREEP-rich volcanism on the Moon - Mu-Han Yang; Qian W.L. Zhang; Qiu-Li Li; Ross N. Mitchell; Richard W. Carlson; Zhu-Yin Chu; Yu Liu; Yi Chen; Shun Guo; Ding-Shuai Xue; Bin Su; Xu Tang; et al. (Science Bulletin, 2025)

Astaxanthin ameliorates Cr (VI) accumulation, antioxidant, digestive, apoptosis and inflammatory response - Lei Zhao; Ying Zhang; Jie Yu; Yi-Han Liu; Zhi-Hao Cai; Mu-Yang Li; Ming Liu (Regional Studies in Marine Science, 2025)

A pair of lignans isolated from Trachelospermum jasminoides and their anti-inflammatory activity - Chen-Yi Yan; Miao Wang; Yu-Ting Mu; Li-Lian Zhao; Yu-Liang Guo; Wei-Zhen Dong; Yun Deng; Da-Le Guo (Phytochemistry Letters, 2025)

Global changes in potential evapotranspiration (1992–2020) and associated drivers: Shuttleworth-Wallace model-based analysis - Zaoying Bi; Shanlei Sun; Yi Liu; Ge Sun; Mengyuan Mu; Xiaoyuan Li; Jinjian Li; Yibo Liu; Yang Zhou; Botao Zhou; Haishan Chen (Journal of Hydrology, 2025)

Skeleton engineering of conjugated microporous polymer for highly efficient PM capture in harsh environments - Cailin Guo; Wei Liu; Mengxue Li; Peng Mu; Anli Yi; Zhaoqi Zhu; Rui Jiao; Hanxue Sun; An Li (Journal of Hazardous Materials, 2025)

Development of a CD3ε mAb that can identify and in vitro activate T cells in large yellow croaker (Larimichthys crocea) - Zhichao Fang; Yi Cao; Haokai Chen; Jie Cheng; Ming Geng; Jiong Chen; Yinnan Mu; Kang Li; Jialong Yang; Xiumei Wei (Fish & Shellfish Immunology, 2025)

Water retention curves of a deformable lean clay under various stress ratios: Emphasizing the pore shape effects - Qing-yi Mu; Tian-qi Song; Chao Zhou; Jian-bing Peng (Computers and Geotechnics, 2025)

Versatile, cost-effective and highly-multiplex nucleic acid detection through the Engineered Hairpin Cleavage Amplification (EHCA) strategy - Zhaocheng Liu; Rui Zhang; Yi Zhang; Huijun Mu; Xinyi Jiang; Jian Zou; Tingting Wang; Ying Yin (Chemical Engineering Journal, 2025)

Construction of a Machine Learning-Based Clopidogrel Resistance Risk Prediction Model - Ruo-Ying Wang; Shui-Di Yan; Jian-Qi Zeng; Tong Mu; Ya Yan; Yuan-Yi Zhao; Lin Xie; Li-Li Liu (Cardiovascular Toxicology, 2025)

The Systematic Study on the Effects of Adding Bile Acids and Zinc to Laying Hens’ Diets: From Production Performance to Egg Quality, Trace Element Content, and Intestinal Microorganisms - Shou Kang Cao; Yi Fan Li; Han Chen; Yu Qing Mu; Xue Zhuang Wu (Biological Trace Element Research, 2025)

Alternative splicing of OsNPR3 promoted by the bacterial TAL effectors-targeted splicing regulator OsRBP11 antagonizes OsNPR1 function and enhances disease susceptibility in rice - Xiaochen Chen; Xiaohui Yao; Fang Yan; Shaofang Li; Zuo-Dong Wang; Fu-You Yin; Miao Zhou; Zhen Wang; Lina Qin; Baoguo Zhao; Kai Lu; Liyuan Zhang; et al. (Molecular Plant, 2025)

STING inhibition suppresses butachlor-induced splenic macrophage pyroptosis and M1 polarization via cGAS-STING signaling - Ru-Yang Zhao; Mu-Zi Li; Qi-Qian Wang; Fu-Wei Jiang; Yi Zhao; Jin-Long Li (Journal of Hazardous Materials, 2025)

Exploring Allium mongolicum Regel flavonoids alleviation of deoxynivalenol-induced gut inflammation and flesh-quality improvement based on muscle-intestinal axis in a Channa argus model - Zhe Yu; Zhuang Xiong; Yi Wang; Zhi-Qiang Gao; Ke-Xin Lu; Ying Zhang; Mu-Yang Li; Yuan-Xi Yue (Food Bioscience, 2025)

Enhancing methanogenesis from long-chain fatty acids (LCFA) and enrichment of novel bacteria with resuscitation-promoting factors - Bo Fang; Yi-Fan Liu; Hao-Xun Wei; Lei Zhou; Shi-Zhong Yang; Ji-Dong Gu; Bo-Zhong Mu (Bioresource Technology, 2025)

Accelerated C-F bond cleavage on sulfur vacancy-contained CoS2/MoS2 electrode featuring rich H* - Zhenglin Chen; Guangzhen Liu; Yuqi Hong; Lixia Yang; Xuefei Li; Hui Xiao; Yi Mu; Yue Li; Jianping Zou; Shenglian Luo (Journal of Hazardous Materials, 2025)

Novel carbonylomics with stable isotope-coded derivatization for non-targeted analysis of reactive carbonyl species in cooking oils - Chiung-Wen Hu; Yuan-Jhe Chang; Yi-Jhen Wang; Yet-Ran Chen; Marcus S. Cooke; Mu-Rong Chao (Journal of Hazardous Materials, 2025)

Necessity of incorporating realistic land surface parameters for trend analyses of potential evapotranspiration and drought - Shanlei Sun; Yifang Zhang; Mengyuan Mu; Zaoying Bi; Yi Liu; Jinjian Li; Yang Zhou; Xiaoyuan Li; Haishan Chen (Journal of Hydrology, 2025)

Trace elements in Mytella strigata and Perna viridis from three Chinese coastal regions: comparison and safety assessments - Yifei Zhang; Peizhen Ma; Mingjie Mu; Chenxia Zuo; Xiaojie Ma; Yi Zhu; Zhen Zhang (Environmental Geochemistry and Health, 2025)

Characteristics of loess landslides under the effects of faults and rivers and their correlations with geological and surficial evolutionary processes - Qi-qi Liu; Wan-li Xie; Hui Yang; Ming Yan; Rong-sen Zhu; Ke Mu; Yi-lun Chang; Shengjie Di; Xiaoliang He; Xiaomin Liu; Ying Zhang (Bulletin of Engineering Geology and the Environment, 2025)

Coexisting plants restored in karst desertification areas cope with drought by changing water uptake patterns and improving water use efficiency - Lulu Cai; Kangning Xiong; Yuan Li; Ziqi Liu; Dayun Zhu; Hong Liang; Yating Mu; Yi Chen (Journal of Hydrology, 2025)

Facile synthesis of trimetallic compounds based on cobalt and nickel with ammonium fluoride-based complex for energy storage applications - Tsai-Mu Cheng; Pei-Chen Kuo; Yi-Chun Lai; Pin-Yan Lee; Chutima Kongvarhodom; Muhammad Saukani; Sibidou Yougbaré; Hung-Ming Chen; Kuo-Chuan Ho; Lu-Yin Lin (Journal of Environmental Chemical Engineering, 2025)

Extraction of hydroxy safflower yellow A and anhydroxysafflor yellow B from safflower florets using natural deep eutectic solvents: Optimization, biological activity and molecular docking - Chun-Ying Wu; Bao-Rong Wang; Si-Yi Han; Ying-Hua Zhang; Zhi-Shen Mu (Food Bioscience, 2025)

Development of cascade nanoreactors by fusing bone-targeting engineered extracellular vesicles to modulate bone microenvironment for treatment of diabetic osteoporosis - He Yi; Fang Depeng; Chen Xiang; Shen Hongdou; Shao Xiaoyan; Lin Jiaquan; Liu Na; Shen Tao; Wang Chengzhi; Zhang Pan; Peng Rui; Mu Jinglan; et al. (Chemical Engineering Journal, 2025)

Activation of NR2A-Wnt-TLR2 Signaling Axis in Satellite Glial Cells of the Dorsal Root Ganglion Contributes to Neuropathic Pain Induced by Nerve Injury in Diabetic Mice - Yan-Yan Zhang; De-Xin Zhu; Mu-Yun Wang; Ya-Ting Yi; Yu-Heng Feng; Cheng Zhou; Chun-Jie Li; Fei Liu; Jie-Fei Shen (Molecular Neurobiology, 2025)

Roseateles cavernae sp. nov., a Bacterium Isolated from Freshwater of the Old Huanglong Cave in Yunnan Province, South-West China - Yu-Man Zhang; Qian Jiang; Mu-Yao Li; Qing-Yu Miao; Yi-Qing Li; Min Yin; Cui-Ping Miao; Shu-Kun Tang (Current Microbiology, 2025)

Construction of the dynamic measurement algorithm for well inclination and azimuth in strapdown stable platform - Feng Sun; Rui Zhang; Yi-feng Wang; Wei Chen; Hui-dong Mu; Rui-wen Feng (Applied Geophysics, 2025)

The Spatial–Temporal Characteristics of Wave Energy Resource Availability in the China Seas - Rui-Zhe Shen; Cheng-Tao Yi; Yu-Nuo Liu; Lei Wang; Kai Wu; Mu-Yu Chen; Chong-Wei Zheng (Journal of Marine Science and Engineering, 2025)
For coastal nations and regions, wave energy provides a localized energy solution, decreasing dependency on external energy sources and fostering the sustainable development of local economies. Effective wave height occurrence (EWHO) represents the availability of wave energy and is a crucial parameter for site selection for optimal wave energy. This paper systematically analyzes the distribution of EWHO in China seas areas using significant wave height (SWH) data in the fifth generation of ECMWF atmospheric reanalysis (ERA5) and key climate indices. Employing methods such as climate statistical analysis, linear regression, significance testing, and trend analysis, the study highlights the temporal and spatial distribution characteristics, variation trends, and correlations with climate indices of EWHO. This research aims to provide technical assistance and decision support for the development of wave energy at sea. The results indicate the following conclusions: (1) The high EWHO in the China seas is predominantly located in northern Nanhai, southern Donghai, and the eastern waters of the Philippine Islands. The EWHO is highest in winter. (2) The growth trend of EWHO is most notable in the sea area east of the line connecting the Ryukyu Islands, Taiwan, and the northeastern Philippines, peaking in spring and being relatively weak in winter. (3) The correlation between NINO3 and EWHO is most significant in Nanhai and the northeastern waters of the Philippines, peaking in February with correlation coefficients ranging from −0.30 to −0.50.

Sedimentary heavy metal interactions with phytoplankton and zooplankton across the Bohai Sea - Yuqiu Wei; Lun Song; Yuanqing Ma; Jiandong Mu; Wei Yi; Jun Sun; Keming Qu; Zhengguo Cui (Journal of Environmental Management, 2025)

A new control strategy of sulfate-reducing microorganisms and corrosion rate from a high-temperature oil reservoir by nitrate/nitrite coupling with nitrate-reducing bacteria - Lei Zhou; Jie Gao; Yu-Xuan Li; Jun Wu; Biao Wang; Yi-Fan Liu; Shi-Zhong Yang; Ji-Dong Gu; Bo-Zhong Mu (International Biodeterioration & Biodegradation, 2025)

Pantothenic acid alleviates osteoarthritis progression by inhibiting inflammatory response and ferroptosis through the SIRT1/Nrf2 signaling pathway - Yi Liu; Yang Wang; Shengqi Cheng; Jie Mu; Guanchen Yin; Hang Gao (Chemico-Biological Interactions, 2025)

Downregulation of HSPB1 and MGST1 Promotes Ferroptosis and Impacts Immune Infiltration in Diabetic Cardiomyopathy - Yaoli Xie; Bin Liang; Zhijun Meng; Rui Guo; Caihong Liu; Yi Yuan; Wei Mu; Yajing Wang; Jimin Cao (Cardiovascular Toxicology, 2025)

Using waste to treat waste: Coupling of advanced reduction processes and anaerobic fermentation - Xing-Yuan Chen; Yun Niu; Lin Pan; Han-Lin Gu; Wei Gao; Zi-Yi Mu; Li-Li Hu; Wei Zhang (Journal of Water Process Engineering, 2025)

Deep learning-driven reconstruction of PM2.5 vertical profiles: A fusion of lidar and tower data - Zihuai Yi; Yan Xiang; Long Yun; Xi Mu; Zhenyi Chen; Yuanzhu Dong; Feilong Li; Yin Pan; Lihui Lv; Tianshu Zhang; Wenqing Liu (Journal of Cleaner Production, 2025)

Recycled wheat straw biochar enhances nutrient-poor soil: Enzymatic kinetics of carbon, nitrogen, and phosphorus cycling - Qiuting Yan; Haixia Tian; Yi Huang; Xiangli Mu; Guangmu Tang; Haigang Ma; Mallavarapu Megharaj; Wanli Xu; Wenxiang He (Journal of Environmental Management, 2025)

Effects of different lactic acid bacteria on the physicochemical properties, functional characteristics and metabolic characteristics of fermented hawthorn juice - Maozhen Zhao; Yunjuan Mu; Zhiping Shi; Xueqi Wang; Wenhao Liu; Yuhan Zhou; Huaxi Yi; Lanwei Zhang; Zhe Zhang (Food Chemistry, 2025)

Water competition among coexisting plants in rock-dominated habitats of subtropical karst desertification - Lulu Cai; Kangning Xiong; Ziqi Liu; Yuan Li; Dayun Zhu; Yating Mu; Yi Chen; Rong Zhou; Xiaoyu Yan (Agriculture, Ecosystems & Environment, 2025)

3D Heterogeneous Geological Model of Natural Gas Hydrates in Shenhu Area, South China Sea - Langfeng Mu; Dawang Liu; Yi Zhang; Hailong Lu; Shipeng Wei (Journal of Marine Science and Engineering, 2025)
Natural gas hydrates, as a novel clean energy resource, have attracted widespread attention because of their highly complex reservoir properties, fluid distribution, and phase transitions. In particular, the fluid–solid interactions among hydrates, natural gas, water, and other multiphase components, along with phase state transitions influenced by temperature and pressure and the dynamic reservoir responses induced by hydrate decomposition and synthesis, make their study unique. Consequently, accurately predicting the structure and reservoir properties of natural gas hydrates remains a scientific challenge. In this study, high-resolution 3D seismic data, well logging, and core samples from the Shenhu test area in the South China Sea were utilized for stratigraphic correlation and classification. The hydrate, three-phase mixed, and free gas layers were identified as distinct geological bodies, and detailed stratigraphic subdivisions were performed based on hydrate distribution and physical properties. By integrating stochastic and deterministic modeling approaches, a comprehensive hydrate reservoir model, along with temperature and pressure field models, was established. For the first time, a three-dimensional heterogeneous geological model of the hydrate reservoir was developed for the test exploitation area. This model provides a robust geological foundation for hydrate reservoir studies, numerical simulations, and the formulation of efficient exploitation strategies, contributing to the advancement of natural gas hydrate exploration and production.

Comparative Transcriptomic Analysis of Male and Female Gonads in the Zig-Zag Eel (Mastacembelus armatus) - Fangyu Cui; Yuanyuan Wang; Haiyan Liang; Yexin Yang; Zhiyong Jiang; Jiahuan Song; Chao Liu; Yuli Wu; Xidong Mu; Yi Liu (Fishes, 2025)
The zig-zag eel (Mastacembelus armatus) is a unique economic fish species in China and exhibits significant dimorphism of male and female phenotypes. Cultivating all-male seedlings can significantly improve production efficiency. To investigate sex differentiation and gonadal development in M. armatus, high-throughput sequencing technology was used to analyze the transcriptomes of male and female gonads at different developmental stages, both before and after sex differentiation. We identified key genes involved in sex differentiation, male-specific differentially expressed genes (DEGs), including dmrt1, amh, sox9, gsdf, and dmrt2b, and female-biased DEGs, including foxl2, rspo1, gdf9, bmp15, and wnt4. GO and KEGG enrichment analyses revealed that signaling pathways such as MAPK, Wnt, and TGF-β play significant roles in sex differentiation in M. armatus. The expression levels of 13 sex-related genes, including dmrt1, sox9, amh, foxl2, rspo1, and wnt4, were determined by RT–qPCR in addition to RNA sequencing. RT-qPCR validation results were consistent with the transcriptomic data, confirming the reliability of our findings. This research provides valuable insights into the mechanisms of sex differentiation in M. armatus and lays a foundation for developing all-male populations in aquaculture.

Nutrient and stoichiometric characteristics of various organs in three typical desert plants from extreme desert ecosystems - Yi Du; Yulin Zhang; Zhihao Zhang; Yanju Gao; Zhaobin Mu; Waqar Islam; Fanjiang Zeng (Rhizosphere, 2025)

BPDE induces ferroptosis in hippocampal neurons through ACSL3 suppression - Hui He; Tingyu Ji; Yi Lyu; Fengjie Tian; Emily Mu; Sophia Mu; Jinping Zheng (NeuroToxicology, 2025)

Deciphering the key role of biofilm and mechanisms in high-strength nitrogen removal within the anammox coupled partial S0-driven autotrophic denitrification system - Shuyan Yin; Yi-Xuan Wang; Cheng Hou; Jing Wang; Jing Xu; Xinbai Jiang; Dan Chen; Yang Mu; Jinyou Shen (Bioresource Technology, 2025)

Identification of two effective sex-specific DNA markers in silver arowana (Osteoglossum bicirrhosum) - Yi Liu; Jinhui Sun; Chao Liu; Yexin Yang; Yuanyuan Wang; Xidong Mu (Aquaculture, 2025)

Accurate spaceborne waveform simulation in heterogeneous forests using small-footprint airborne LiDAR point clouds - Yi Li; Guangjian Yan; Weihua Li; Donghui Xie; Hailan Jiang; Linyuan Li; Jianbo Qi; Ronghai Hu; Xihan Mu; Xiao Chen; Shanshan Wei; Hao Tang (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Predicting absolute adsorption of CO2 on Jurassic shale using machine learning - Changhui Zeng; Shams Kalam; Haiyang Zhang; Lei Wang; Yi Luo; Haizhu Wang; Zongjie Mu; Muhammad Arif (Fuel, 2025)

Research landmarks on the 60th anniversary of Epstein-Barr virus - Lan-Yi Zhong; Chu Xie; Le-Le Zhang; Yan-Lin Yang; Yuan-Tao Liu; Ge-Xin Zhao; Guo-Long Bu; Xian-Shu Tian; Zi-Ying Jiang; Bo-Yu Yuan; Peng-Lin Li; Pei-Huang Wu; et al. (Science China Life Sciences, 2025)

Development of 68 SSR markers for Hemibagrus guttatus, a protected indigenous catfish in China - Yexin Yang; Yi Liu; Shandian Zhu; Bingyuan Xiong; Yuli Wu; Jiahuan Song; Chao Liu; Xidong Mu (Conservation Genetics Resources, 2025)

Do red marine carbonates represent oxic environments? New understanding from the Upper Ordovician marine limestone in Tarim Basin, China - Mu Liu; Daizhao Chen; Haoran Ma; Yi Ding (Marine and Petroleum Geology, 2025)

Microbiome changes and characteristics under nutrient injection for enhanced oil production at Daqing oilfield - Zi-Yue Fu; Wen-Tao Chen; Gui-Na Qi; Zhao-wei Hou; Yi-Fan Liu; Li-Bin Shou; Lei Zhou; Shi-Zhong Yang; Xiao-Lin Wu; Ji-Dong Gu; Bo-Zhong Mu (International Biodeterioration & Biodegradation, 2025)

A comprehensive study on fermentation and aroma contributions of Torulaspora delbrueckii in diverse wine varieties: Insights from pure and co-fermentation studies - Yichao Cheng; Shijin Geng; Jin Zhang; Xixi Zhao; Jiao Jiang; Yanying Liang; Haibin Mu; Wenchao Li; Yi Qin; Yanlin Liu; Yuyang Song (Food Research International, 2025)

Phase-separated anisotropic PVA hydrogel loaded with tetramethylpyrazine for spinal cord injury repair - Gang Liu; Shenglin Li; Bowen Deng; Luyao Huo; Huizhong Bai; Shengyuan Jiang; Yimin Zhou; Zhenzhen Pei; Ceren Kimna; Yi Zhao; Lin Xu; Jinyu Li; et al. (Chemical Engineering Journal, 2025)

Enhanced detection of mango leaf diseases in field environments using MSMP-CNN and transfer learning - Yi-Chen Chen; Jen-Cheng Wang; Mu-Hwa Lee; An-Chi Liu; Joe-Air Jiang (Computers and Electronics in Agriculture, 2024)

Highly dispersed CuOx decorated ZnO photocatalyst for low-concentration methane removal - Yun Wang; Sheng Xu; Haiyuan Zhang; Yuyin Wang; Enmao Wang; Zeyu He; Jiahua Zhu; Xiaohua Lu; Lilong Zhang; Yang Bai; Kunfeng Zhao; Qingwei Gao; et al. (Journal of Environmental Chemical Engineering, 2024)

Dissecting changes in evapotranspiration and its components across the Losses Plateau of China during 2001–2020 - Shanlei Sun; Aoge Ma; Yibo Liu; Menyuan Mu; Yi Liu; Yang Zhou; Jinjian Li (International Journal of Climatology, 2024)
China's Losses Plateau (LP) is one of the ecologically vulnerable and the most severe soil erosion regions. Thus, knowing spatiotemporal changes in evapotranspiration (ET) and its components (soil evaporation, E; transpiration, T; and vegetation interception evaporation, EI) and revealing the underlying mechanisms are vital for ecosystem and water resources sustainability for this region. Here, we investigate the spatiotemporal changes in ET and its components and then quantify the impacts of climate variables (i.e., precipitation, radiation, temperature, and relative humidity) and vegetation dynamics (e.g., land use/cover changes [LUCC] and changes in leaf area index [LAI]) on their annual trends, by using a process‐based terrestrial ecosystem model and a joint‐solution method with multiple sensitivity numerical experiments. Results show that over 67% of the study region experienced significant ( p −1 , respectively. However, there are significant ( p −1 , and the negative trend covers 35.8% of the study area. E, T, and EI changes dominate the annual ET trends over 11.8%, 87.3%, and 0.9% of the study area, respectively. Attribution analyses highlight the increased LAI as the critical factor governing these trends across most of the LP (>58%). At the same time, precipitation and LUCC play a more dominant role in the remaining areas. This study emphasizes the spatial heterogeneity in the drivers of changes in ET and its components and highlights the critical role of vegetation dynamics. These findings provide valuable insights for understanding the ET processes and guiding sustainable water resource management in the LP.

Boosting bioelectricity generation in bioelectrochemical systems with nitrogen-doped three-dimensional graphene aerogel anode - Yi-Xuan Wang; Xiao-Li Liu; Wen-Qiang Li; Yi-Ran Wang; Ke-Wan Li; Zhi-Cheng Pan; Yang Mu (Water Research, 2024)

Depth-dependent responses of soil bacterial communities to salinity in an arid region - Xinping Dong; Zhihao Zhang; Yan Lu; Li Li; Yi Du; Akash Tariq; Yanju Gao; Zhaobin Mu; Yuhe Zhu; Weiqi Wang; Jordi Sardans; Josep Peñuelas; et al. (Science of The Total Environment, 2024)

Characterization of SCOBY-fermented kombucha from different regions and its effect on improving blood glucose - Yang Meng; Xueqi Wang; Yunjuan Mu; Maozhen Zhao; Yujia Liu; Huaxi Yi; Lanwei Zhang; Zhe Zhang (Food Bioscience, 2024)

Injectable NGF-loaded double crosslinked collagen/hyaluronic acid hydrogels for irregular bone defect repair via neuro-guided osteogenic process - Qingsong Jiang; Liaomin Zhou; Yi Yang; Hu Long; Liming Ge; Defu Li; Changdao Mu; Wenli Lai; Zhilang Xu; Yan Wang (Chemical Engineering Journal, 2024)

Evaluation of the collapse susceptibility of loess using machine learning - Qing-yi Mu; Tian-qi Song; Zhao Lu; Te Xiao; Li-min Zhang (Transportation Geotechnics, 2024)

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

Essential trace element and phosphatidylcholine remodeling: Implications for body composition and insulin resistance - Wen-Ling Lin; Mu-Ming Chien; Sangopas Patchara; Weu Wang; Amelia Faradina; Shih-Yi Huang; Te-Hsuan Tung; Chien-Sung Tsai; Anatoly V. Skalny; Alexey A. Tinkov; Chun-Chao Chang; Jung-Su Chang (Journal of Trace Elements in Medicine and Biology, 2024)

Implications of ocean warming and acidification on heavy metals in surface seawater of the Bohai Sea - Yuqiu Wei; Lun Song; Yuanqing Ma; Jiandong Mu; Wei Yi; Jun Sun; Keming Qu; Zhengguo Cui (Journal of Hazardous Materials, 2024)

Multi-objective optimization of clean utilization for zinc leaching residues by rotary kiln using neural network coupled modeling - Chen-Mu Zhang; Zhi Zan; Yao Shi; Hui-Quan Li; Lang-Ming Liu; Wei-Ping Liu; Wen-Jun Lin; Jing-Jing Shi; Ying-yan Hu; Xue Guan; Kuang-Yi Chen; Xiao Liu; et al. (Journal of Cleaner Production, 2024)

A culture-dependent analysis of anaerobic methylotrophs in oil reservoir systems - Lin-Yuan Huang; Yi-Fan Liu; Wan-Qi Qin; Shi-Yi Wang; Yuan-Hao Wang; Lei Zhou; Shi-Zhong Yang; Ji-Dong Gu; Bo-Zhong Mu (International Biodeterioration & Biodegradation, 2024)

Continuous flow hydrothermal synthesis of MoVNbTeOx in micro-coil tubular reactor for oxidative dehydrogenation of ethane - Yuxin Chen; Yuting Wu; Shuairen Qian; Zhengwen Li; Changyan Xu; Ruiqi Du; Yao Mu; Tianying Dai; Binhang Yan; Yi Cheng (Chemical Engineering Journal, 2024)

Dimeric piperidinoquinoline alkaloids from the seeds of Chimonanthus salicifolius - Zhan-Peng Yu; Yu-Xia Wang; Li-Hong Hong; Ya-Lin Li; Jian-Fei Zhang; Mu Li; Ping Ying; Qiang Zheng; Ling-Yi Kong; Jian-Guang Luo (Phytochemistry Letters, 2024)

Methanogenic biodegradation of thermoplastic poly(vinyl alcohol) films produced by two manufacturing processes in enrichment cultures - Ming-Le Ji; Yi-Fan Liu; Yu Bai; Zhen Hu; James H. Wang; Jia-Yi Li; Wan-Qi Qin; Lei Zhou; Shi-Zhong Yang; Ji-Dong Gu; Yingcheng Li; Bo-Zhong Mu (International Biodeterioration & Biodegradation, 2024)

Preparation, taste characterization, and evaluation of oyster composite products with increased umami and salty - Baifeng Fu; Shuzhen Cheng; Xin Zhang; Junjie Yi; Zhishen Mu; Ming Du (Food Bioscience, 2024)

Synthesis of N-vinylcarbazole from acetylene by a continuous high-pressure liquid-phase process with inherent safety - Yao Mu; Jiahe Fan; Bozhao Chu; Siqing Zhong; Yi Cheng (Chemical Engineering Journal, 2024)

Vertical transmission of aerosols between building flats through drainage system: A review - Min Chang; Di Mu; Yi Zhao; Lingjun Xiao; Yan Wu; Naiping Gao (Building and Environment, 2024)

Circ-IP6K2 suppresses tumor progression by modulating the miR-1292-5p/CAMK2N1 signal in clear cell renal cell carcinoma - Jian-ying Tang; Lu Yang; Qing-Jian Wu; Ying Yang; Yuan-Yuan Su; Yi-Rong Chen; Jiao Mu (Functional & Integrative Genomics, 2024)

Upcycling of waste polycarbonate to recyclable Poly(carbonate-imines) with exceptional thermal properties and unprecedented flame retardancy - Yi-Chun Chen; Pin-Qi Mu; Kamani Sudhir K. Reddy; Ru-Jong Jeng; Mahdi M. Abu-Omar; Ching-Hsuan Lin (Chemical Engineering Journal, 2024)

Boosting persulfate activation through efficient π → π* transition activated by Cu ion anchored porphyrin-based metal–organic framework - Wen-Qiang Li; Oleksandr Savateev; Yuan-Ming Li; Jian-Kang Zheng; Yi-Xuan Wang; Nannan Hou; Xiao-Cheng Liu; Rong-Rong Ding; Xiao-Guo Zhou; Yang Wang; Xian-Yang Shi; Yang Mu (Chemical Engineering Journal, 2024)

Pressure/temperature-assisted crystallographic engineering–A strategy for developing the infrared phosphors - Yi-Ting Tsai; Tadeusz Leśniewski; Natalia Majewska; Mikołaj Kamiński; Justyna Barzowska; En-Pei Liu; Wei-Tin Chen; Sebastian Mahlik; Mu-Huai Fang (Chemical Engineering Journal, 2024)

Identification and Characterization of microRNAs in Morphological Color Change of Polychromatic Midas Cichlids (Amphilophus citrinellus) - Guoqiang Wu; Xidong Mu; Yi Liu; Chao Liu; Xuejie Wang; Yexin Yang; Hongmei Song (Fishes, 2024)
As a representative genetic and economic trait, pigmentation has a strong impact on speciation and adaptation. However, information and reports on microRNAs (miRNAs) associated with pigmentation remain limited. The Midas cichlid fish, with three typical distinct stages of body color pattern, “black-gray-gold”, is an ideal model system for investigating pigmentation traits. In this study, miRNA libraries from scale tissues with the attached epidermis of Midas cichlids at three distinct stages of color transformation, black (B), transition (T), and gold (G), were sequenced using Illumina sequencing technology. In total, 53 (B vs. G), 88 (B vs. T), and 57 (T vs. G) miRNAs were differentially expressed between the respective groups. Target genes of the identified miRNAs were predicted, and the results showed that multiple target genes were related to pigmentation and pigment–cell differentiation. The miRNA–mRNA regulatory network suggests that miR-183-x and miR-133-x were predicted to be involved in regulating morphological color changes in Midas cichlids. The results advance our understanding of potential functions of miRNAs in skin pigment differentiation and early skin color fading of fishes.

Alkaloids from the stems of Fissistigma maclurei Merr. inhibit the proliferation of synoviocytes - Mu-Tao Liang; Xiao-Zheng Zhang; Zi-Hao Chen; Chuan-Shan Fu; Duo-Jiang Li; Guo-Ze Chen; Ji-Ling Yi; Xue-Ming Zhou (Natural Product Research, 2024)

Social determinants of health and their relation to suboptimal health status in the context of 3PM: a latent profile analysis - Lai Kun Tong; Yue Yi Li; Yong Bing Liu; Mu Rui Zheng; Guang Lei Fu; Mio Leng Au (EPMA Journal, 2024)

Material and microbial perspectives on understanding the role of biochar in mitigating ammonia inhibition during anaerobic digestion - Zhi-Jun Zhao; Xiao-Li Liu; Yi-Xuan Wang; Yan-Shan Wang; Jin-You Shen; Zhi-Cheng Pan; Yang Mu (Water Research, 2024)

Graphene oxide quantum dots (GOQDs) induce behavioral disorders via the disturbance of kynurenine pathway in zebrafish larvae - Shun Deng; Enming Zhang; Yunyang Zhao; Hao Guo; Lan Luo; Song Yi; Bingxin Zheng; Xiaoyuan Mu; Kezhu Yuan; Xuangen Deng; Haibo Rong; Yanbo Ma; et al. (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2024)

IRE1α: from the function to the potential therapeutic target in atherosclerosis - Zheng-Yang Zhou; Li Wu; Yi-Fan Liu; Mu-Yao Tang; Jing-Yi Tang; Ya-Qian Deng; Lei Liu; Bin-Bin Nie; Zi-Kai Zou; Liang Huang (Molecular and Cellular Biochemistry, 2024)

Tetramethylpyrazine inhibits the inflammatory response by downregulating the TNFR1/IκB-α/NF-κB p65 pathway after spinal cord injury - Gang Liu; Luyao Huo; Bowen Deng; Shengyuan Jiang; Yi Zhao; Yanjun Mo; Huizhong Bai; Lin Xu; Chuanyu Hu; Xiaohong Mu (Toxicology and Applied Pharmacology, 2024)

Scalable, mechanically-robust, fire-resistance MXene/PEDOT:PSS/PBO film for efficient electromagnetic interference shielding and Joule heating performance - Haorui Duan; Chuanshen Wang; Yuxiang Yi; Xiaowei Mu; Hongliang Ding; Zhuyun Bi; Yuan Hu; Bin Yu (Chemical Engineering Journal, 2024)

Acetylenic spiroketal enol ethers from Artemisia rupestris and their synergistic antibacterial effects on methicillin-resistant Staphylococcus aureus - Chuan-Yun Xiao; Jiang-Er Lan; Xiao Liu; Zhong-Lin Sun; Xiao-Jin Li; Yi-Han Yin; Simon Gibbons; Qing Mu (Natural Product Research, 2024)

Melatonin inhibits atrazine-induced mitochondrial impairment in cerebellum of mice: Modulation of cGAS-STING-NLRP3 axis-dependent cell pyroptosis - Lin Liu; Mu-Zi Li; Ming-Hui Yao; Tian-Ning Yang; Yi-Xi Tang; Jin-Long Li (Science of The Total Environment, 2024)

Tracing magmatic differentiation of peralkaline granites by using K stable isotopes - Hang Xu; Weiqiang Li; Xiao-Lei Wang; Jun Mu; De-Hong Du; Jiao-Long Zhao; Ding-Yi Xiong (Geochimica et Cosmochimica Acta, 2024)

Construction of and evaluation of the immune response to two recombinant pseudorabies viruses expressing the B119L and EP364R proteins of African swine fever virus - Xin-Mei Geng; Ying-Mu Xi; Xiang-Mei Huang; Yang-Lin Wang; Xu-Ying Wang; Kang Ouyang; Ying Chen; Zu-Zhang Wei; Yi-Feng Qin; Wei-Jian Huang (Archives of Virology, 2024)

Effects of different visible light spectrums on phototaxis and bottom preference behavior of sea cucumber - Mu-Hsiang Wang; Yi-Jui Hsieh; Hsiu-Hua Chang; Yung-Song Wang (Aquaculture, 2024)

Sustainable development of the mining sector for achieving common prosperity in Chinese rural areas - Yiru Chen; Mu He; Yi Xu (Resources Policy, 2023)

Modeling the long-term transport and fate of oil spilled from the 2021 A Symphony tanker collision in the Yellow Sea, China: Reliability of the stochastic simulation - Ruichen Cao; Zengrui Rong; Haibo Chen; Yi Liu; Lin Mu; Xianqing Lv (Ocean Modelling, 2023)

Heterostructured YFeO3/CeO2 as efficient photoelectrode for photoelectrochemical degradation of organic pollutants under visible light irradiation - Yen-Shen Kuo; Mu-Jung Lin; Cheng-Liang Hsu; Yi-Hung Liu (Journal of Water Process Engineering, 2023)

High-performance inkjet-printed inverted QD-LEDs based on cross-linkable electron regulation layers - Liming Xie; Qing Li; Yuan-Qiu-Qiang Yi; Gengrui Qiu; Omolola Esther Fayemi; Xinju Mu; Zhongsheng Ma; Pengyu Tang; Yang Liu; Wenming Su; Wei Lei; Zheng Cui (Chemical Engineering Journal, 2023)

Geochronology and in-situ apatite geochemistry of late Paleoproterozoic A-type granites in the Jiao-Liao-Ji Belt, North China Craton: Implications for petrogenesis and tectonic evolution - Yi-Kang Quan; Mao-Song Mu; De-Bin Yang; Xiang-Yu Yan; An-Qi Wang; Le-Ran Hao; Feng Wang (Geochemistry, 2023)

Graphene-based biomimetic array film for simultaneous fog water harvesting and wind power generation - Tsung Han Huang; Mu-Jie Shih; Yi-Yun Chen; Hannah Faye M. Austria; Owen Setiawan; Chunrui Wu; Xiaolong Lu; Lin Zhang; Wei-Song Hung (Chemical Engineering Journal, 2023)

Enhanced biological phosphorus removal by high concentration powder carrier bio-fluidized bed (HPB): Phosphorus distribution, cyclone separation, and metagenomics - Yanyu Mu; Li Wan; Zixuan Liang; Donghai Yang; Hongbo Han; Jing Yi; Xiaohu Dai (Chemosphere, 2023)

Review on fault-tolerant control of unmanned underwater vehicles - Fuqiang Liu; Zuxing Ma; Bingxian Mu; Chaoqun Duan; Rui Chen; Yi Qin; Huayan Pu; Jun Luo (Ocean Engineering, 2023)

The molecular basis of heat stress responses in plants - Yi Kan; Xiao-Rui Mu; Jin Gao; Hong-Xuan Lin; Youshun Lin (Molecular Plant, 2023)

PANI grafted onto waste poros polyurethane for co-adsorption of multiple pollutants in industrial wastewater - Ning Wang; Yirui Guo; Yi Song; Wei Yan; Xuesong Gong; Yunfeng Li; Rui hua Mu; Yonghong Liu; Luohong Zhang (Journal of Water Process Engineering, 2023)

Enhanced retention of surface-adsorbed atomic hydrogen through sulfidation of nano zerovalent iron for water decontamination - Guan-Nan Zhou; Jia-Qi Chen; Wen-Qiang Li; Chuan-Shu He; Li Gong; Xiao-Cheng Liu; Yi-Ran Wang; Dahong Huang; Yang Mu (Chemical Engineering Journal, 2023)

Dendrobium officinale polysaccharides improved reproductive oxidative stress injury in male mice treated with cyclophosphamide - Yi Mu; Bangwei Che; Kaifa Tang; Wenjun Zhang; Shenghan Xu; Wei Li; Jun He; Miao Liu; Peng Chen; Siwen Zhong; Guangyu Li (Environmental Science and Pollution Research, 2023)

Correction: Three-Dimensional Digital Reconstruction of the Cerebellar Cortex: Lobule Thickness, Surface Area Measurements, and Layer Architecture - Junxiao Zheng; Qinzhu Yang; Nikos Makris; Kaibin Huang; Jianwen Liang; Chenfei Ye; Xiaxia Yu; Mu Tian; Ting Ma; Tian Mou; Wenlong Guo; Ron Kikinis; et al. (The Cerebellum, 2023)

Molecular mechanism by which StSN2 overexpression inhibits the enzymatic browning of potato - Li-qin Li; Yu-lu Mu; Jing Chen; Qiang Wang; Yi-fei Lu; Sun Xin; Shi-min Yang; Xue-li Huang; Xi-yao Wang; Li-ming Lu (Postharvest Biology and Technology, 2023)

Opportunities and challenges in Asian bee research and conservation - Natapot Warrit; John Ascher; Parthib Basu; Vasuki Belavadi; Axel Brockmann; Damayanti Buchori; James B. Dorey; Alice Hughes; Smitha Krishnan; Hien T. Ngo; Paul Williams; Chao-Dong Zhu; et al. (Biological Conservation, 2023)

Endoplasmic reticulum stress: a vital process and potential therapeutic target in chronic obstructive pulmonary disease - Hao Peng; Qing Zhou; Jing Liu; Yi Wang; Ketao Mu; Lei Zhang (Inflammation Research, 2023)

Highly sensitive detection of microRNA-21 by nitrogen-doped carbon dots-based ratio fluorescent probe via nuclease-assisted rolling circle amplification strategy - Shan Huang; Bo Li; Pingping Mu; Wenqian Zhang; Yi Liu; Qi Xiao (Analytica Chimica Acta, 2023)

Transcriptomic analysis of the fat body of resistant and susceptible silkworm strains, Bombyx mori (Lepidoptera), after oral treatment with fenpropathrin - Zi-qin Zhao; Kai-yi Zheng; Yu-tong Zhu; Jun-li Lv; Zhi-hao Su; Xiao-ying Zhang; Wen-qing Lai; Mu-wang Li; Yang-chun Wu; Xue-yang Wang (Pesticide Biochemistry and Physiology, 2023)

Maximizing jet fuel production from n-hexadecane hydrocracking over Pt-supported Y catalysts: Importance of ideal hydrocracking characteristics - Yi Li; Chao Mu; Guangxin Chu; Yule Wang; Jing Xu; Xuan Guo; Yujun Zhao; Shengping Wang; Xinbin Ma (Fuel, 2023)

Lead(II)-triggered aggregation-induced emission enhancement of adenosine-stabilized gold nanoclusters for enhancing photoluminescence detection of nabam—disodium ethylenebis(dithiocarbamate) - Qianfen Zhuang; Chao Zeng; Yaxin Mu; Tao Zhang; Guotao Yi; Yong Wang (Chemical Engineering Journal, 2023)

Intrageneric Relationship of Datnioides (Lobotiformes) Inferred from the Complete Nuclear Ribosomal DNA Operon - Yuanyuan Wang; Hong Zhou; Yexin Yang; Jinhui Sun; Yi Liu; Chao Liu; Sudong Xia; Xidong Mu (Biochemical Genetics, 2023)

Short-chain fatty acids (SCFAs) as potential resuscitation factors that promote the isolation and culture of uncultured bacteria in marine sediments - Chun-Shui Sun; Liu-Yan Zhou; Qi-Yun Liang; Xiao-Man Wang; Yi-Xuan Lei; Zhen-Xing Xu; Feng-Qing Wang; Guan-Jun Chen; Zong-Jun Du; Da-Shuai Mu (Marine Life Science & Technology, 2023)
Many marine bacteria are difficult to culture because they are dormant, rare or found in low-abundances. Enrichment culturing has been widely tested as an important strategy to isolate rare or dormant microbes. However, many more mechanisms remain uncertain. Here, based on 16S rRNA gene high-throughput sequencing and metabolomics technology, it was found that the short-chain fatty acids (SCFAs) in metabolites were significantly correlated with uncultured bacterial groups during enrichment cultures. A pure culture analysis showed that the addition of SCFAs to media also resulted in high efficiency for the isolation of uncultured strains from marine sediments. As a result, 238 strains belonging to 10 phyla, 26 families and 82 species were successfully isolated. Some uncultured rare taxa within Chlorobi and Kiritimatiellaeota were successfully cultured . Amongst the newly isolated uncultured microbes, most genomes, e.g. bacteria, possess SCFA oxidative degradation genes, and these features might aid these microbes in better adapting to the culture media. A further resuscitation analysis of a viable but non-culturable (VBNC) Marinilabiliales strain verified that the addition of SCFAs could break the dormancy of Marinilabiliales in 5 days, and the growth curve test showed that the SCFAs could shorten the lag phase and increase the growth rate. Overall, this study provides new insights into SCFAs, which were first studied as resuscitation factors in uncultured marine bacteria. Thus, this study can help improve the utilisation and excavation of marine microbial resources, especially for the most-wanted or key players.

Indoxyl sulfate in atherosclerosis - Cong Lu; Li Wu; Mu-Yao Tang; Yi-Fan Liu; Lei Liu; Xi-Ya Liu; Chun Zhang; Liang Huang (Toxicology Letters, 2023)

Composition and transcriptional activity of oil reservoir microorganisms under different gas/liquid ratios - Li-Bin Shou; Zhao-Wei Hou; Yi-Fan Liu; Ying Wang; Lei Zhou; Jin-Feng Liu; Shi-Zhong Yang; Ji-Dong Gu; Xiao-Lin Wu; Bo-Zhong Mu (International Biodeterioration & Biodegradation, 2023)

Short-term effects of individual exposure to PM2.5 on hospital admissions for myocardial infarction and stroke: a population-based case-crossover study in Guangzhou, China - Jie-Qi Jin; Guo-Zhen Lin; Shuang-Ying Wu; Mu-Rui Zheng; Hui Liu; Xiang-Yi Liu; Min-Qian Yan; Zhao-Yue Chen; Chun-Quan Ou (Environmental Science and Pollution Research, 2023)

Spatial differences in impacts of CO2 effect on China’s meteorological droughts: Analysis from surface resistance perspective - Shanlei Sun; Yifang Zhang; Rongfan Chai; Yi Liu; Mengyuan Mu; Botao Zhou; Yang Zhou; Jinjian Li; Haishan Chen (Journal of Hydrology, 2023)

Organic geochemical characteristics and organic matter accumulation of the Eocene lacustrine source rock in the Yingxi area, Western Qaidam Basin, China - Fan Yi; Haisheng Yi; Chuanlong Mu; Wenqiang Tang; Na Li; Yun Chen; Kangzhi Tian; Yuxiang Shi; Jinxuan Wu; Guoqing Xia (International Journal of Earth Sciences, 2023)

Effects of solar radiation and fine roots on suction of Amorpha fruticose-vegetated soil - Han-qing Guo; Xiao-qing Chen; Dong-ri Song; Qing-yi Mu; Hamed Sadeghi; Hao Jiang; Ming Lv (Journal of Mountain Science, 2023)

Inducing itinerant ferromagnetism by manipulating van Hove singularity in epitaxial monolayer 1T-VSe2 - Junyu Zong; Zhao-Yang Dong; Junwei Huang; Kaili Wang; Qi-Wei Wang; Qinghao Meng; Qichao Tian; Xiaodong Qiu; Yuyang Mu; Li Wang; Wei Ren; Xuedong Xie; et al. (Science Bulletin, 2023)

5-epi-ent-Kaurane diterpenoids from the aerial parts of Isodon eriocalyx and their anti-atherosclerotic potential - Long Mu; Tian Li; Peng-Lin Wu; Ling-Qiao Cai; Shu-Ying Li; Zi-Yuan Wang; Yuan-Yuan Liu; Jie Wang; Dong Yan; Zheng-Yun Rao; Chao-Jun Wang; Jian Zhang; et al. (Phytochemistry, 2023)

Population genetics of zig-zag eel (Mastacembelus armatus) uncover gene flow between an isolated island and the mainland China - Yexin Yang; Yuanyuan Wang; Yuli Wu; Yi Liu; Chao Liu; Zhiyong Jiang; Xidong Mu (Frontiers in Marine Science, 2023)
Introduction Mastacembelus armatus is a commercially valuable fish, normally distributed in southern China and Southeast Asia. The natural population size of M. armatus is shrinking in recent years because of overfishing and habitat loss. In order to clarify the genetic diversity and differentiation of M. armatus populations, we collected 114 samples from eight populations in southern China and Vietnam and analyzed their population structure using nuclear ribosomal DNA sequences, the concatenated 18S and ITS2 regions. Methods Genomic DNA from the fin clip was extracted and sequenced on an Illumina novaseq 6000 (Illumina, USA) high-throughput sequencing platform in accordance with the manufacturer’s instructions. After assembly and annotation, haplotype diversity, TCS network analysis, AMOVA analysis, population pairwise genetic distances, and UPGMA tree construction were conducted based on the concatenated sequences of 18S and ITS2. Results and discussion In total, eleven nrDNA haplotypes were detected based on the concatenated sequences of 18S and ITS2. Amongst, three haplotypes were the main haplotypes, as representatives of three corresponding Clusters. There were two major Clusters in China, however, the Cluster in Vietnam was significantly divergent from the other two in China, likely due to the lack of river connection between China and Vietnam. Interestingly, based on low FST value, we found that gene flow occurred between the isolated island, Hainan Province, and the mainland China of Guangxi Province, probably as a result of exposed continental shelf connected them during glacial periods. In general, combing our data and literature data, genetic diversity and differentiation of M. armatus populations are relatively high regardless of spatial scale, although their natural population size is declining. This suggests that it is not too late to adopt measures to protect M. armatus, which benefits not only species itself but also the whole ecosystem.

Comprehensive analysis for the bioturbation effect of space mutation and biofortification on strong-flavor Daqu by high-throughput sequencing, volatile analysis and metabolomics - Yu Mu; Jun Huang; Rongqing Zhou; Suyi Zhang; Hui Qin; Yi Dong; Chao Wang; Xiaojun Wang; Qianglin Pan; Huifang Tang (Food Chemistry, 2023)

Coupling coordination relationships between air pollutant concentrations and emissions in China - Qian Wu; Song Hong; Lu Yang; Hang Mu; Chaoqing Huang; Xiaoxiao Niu; Yanmei Zhong; Jiahui Yi; Chao He (Atmospheric Pollution Research, 2023)

Deep Sc-RNA sequencing decoding the molecular dynamic architecture of the human retina - Lulin Huang; Runze Li; Lin Ye; Shanshan Zhang; Huaping Tian; Mingyan Du; Chao Qu; Shujin Li; Jie Li; Mu Yang; Biao Wu; Ran Chen; et al. (Science China Life Sciences, 2023)

Bidirectional reflectance factor measurement of conifer needles with microscopic spectroscopy imaging - Yongkang Lai; Xihan Mu; Yuequn Bian; Xiaohan Dong; Feng Qiu; Xinyu Bo; Zhixiang Zhang; Yi Li; Xinli Liu; Linyuan Li; Donghui Xie; Guangjian Yan (Agricultural and Forest Meteorology, 2023)

Characteristics of microbiota, core sulfate-reducing taxa and corrosion rates in production water from five petroleum reservoirs in China - Lei Zhou; Jun Wu; Jia-Heng Ji; Jie Gao; Yi-Fan Liu; Biao Wang; Shi-Zhong Yang; Ji-Dong Gu; Bo-Zhong Mu (Science of The Total Environment, 2023)

Structures of the xyloglucans in the monocotyledon family Araceae (aroids) - Shih-Yi Hsiung; Jing Li; Balazs Imre; Mu-Rong Kao; Hsien-Chun Liao; Damao Wang; Chih-Hui Chen; Pi-Hui Liang; Philip J. Harris; Yves S. Y. Hsieh (Planta, 2023)
Main conclusion The xyloglucans of all aquatic Araceae species examined had unusual structures compared with those of other non-commelinid monocotyledon families previously examined. Abstract The aquatic Araceae species Lemna minor was earlier shown to have xyloglucans with a different structure from the fucogalactoxyloglucans of other non-commelinid monocotyledons. We investigated 26 Araceae species (including L. minor ), from five of the seven subfamilies. All seven aquatic species examined had xyloglucans that were unusual in having one or two of three features: < 77% XXXG core motif [ L. minor (Lemnoideae) and Orontium aquaticum (Orontioideae)]; no fucosylation [ L. minor (Lemnoideae), Cryptocoryne aponogetonifolia , and Lagenandra ovata (Aroideae, Rheophytes clade)]; and > 14% oligosaccharide units with S or D side chains [ Spirodela polyrhiza and Landoltia punctata (Lemnoideae) and Pistia stratiotes (Aroideae, Dracunculus clade)]. Orontioideae and Lemnoideae are the two most basal subfamilies, with all species being aquatic, and Aroideae is the most derived. Two terrestrial species [ Dieffenbachia seguine and Spathicarpa hastifolia (Aroideae, Zantedeschia clade)] also had xyloglucans without fucose indicating this feature was not unique to aquatic species.

Biofertilizer made from a mixed microbial community can enhance the suppression of fusarium wilt of banana when combined with acid soil ameliorant - Jianfeng Huang; Yuwan Pang; Gen Cheng; Tengfei Wu; Qiaoyi Huang; Xu Huang; Qiong Yi; Mu Zhang; Shuanhu Tang; Hongting Fu; Ping Li (European Journal of Plant Pathology, 2023)

The Origin and Preservation of Suspended Barites near the 90°E Ridge in the Northeastern Indian Ocean - Xuejiao Bu; Ming Liu; Yi Ding; Yadi Yang; Mu Huang; Xiaoxia Sun; Dejiang Fan; Zuosheng Yang (Journal of Ocean University of China, 2023)

dmrt3, nom1, abce1, and pkmyt1 play key roles in gonadal sex determination in Acrossocheilus fasciatus - Yuting Ren; Yi Mu; Bo Zhao; Yang Gao; Xiaoxin Dai; Zhangjie Chu (Aquaculture International, 2023)

Influence of ionized saline water on soil water and salt transport in saline soils - Kai Wei; Shudong Lin; Jihong Zhang; Quanjiu Wang; Yi Guo; Weiyi Mu (Irrigation and Drainage, 2023)
The utilization of saline water plays an important role in agricultural production in saline areas to overcome freshwater shortages. Ionized saline water might alleviate the adverse effects of salinity on soil and plants. In this study, field experiments were conducted to study the effect of ionized saline water on the soil water content and salinity distribution in a sandy soil under a surface emitter. Passing groundwater through an ionization system installed on a feeding pipeline resulted in producing ionized saline water. Three emitter discharges (1.0, 1.8, 3.1 L h −1 ) and two water types (non‐ionized and ionized saline water) were considered in the experiments. As a result of using ionized saline water, soil water content and salt leaching increased. Ionized treatment increased the salinity desalination rate by 31, 33 and 26% for surface soil layer in comparison with non‐ionized treatments of 1.0, 1.8 and 3.1 L h −1 , respectively. It was found that using ionized saline water could decrease the surface wetting radius by 6–9% and increase the wetting depth by 11–17%. A discharge rate of 1.8 L h −1 was recommended as the optimal discharge rate for ionized saline water under drip irrigation. The results indicated that saline water could be improved through ionized treatment for agricultural irrigation in saline soils in an arid region.

Xenobiotic-sensing nuclear receptors as targets for phthalates-induced lung injury and antagonism of lycopene - Yu-Sheng Shi; Yi Zhao; Xue-Nan Li; Mu-Zi Li; Jin-Long Li (Chemosphere, 2023)

Short-term microbial effects on n-alkane during the early phase degradation and consequential modification of biomarkers in a lowland subtropical rainforest in southern Taiwan: A litterbag experiment - Bing-Mu Hsu; Jung-Sheng Chen; Tung-Yi Huang; Bashir Hussain; Wei-Chun Chao; Cheng-Wei Fan (Journal of Environmental Management, 2023)

Characterizing the spatiotemporal distribution of dissolved organic matter (DOM) in the Yongding River Basin: Insights from flow regulation - Yijuan Bai; Shurong Zhang; Enlin Mu; Yinjun Zhao; Lirong Cheng; Yi Zhu; Yumin Yuan; Yingying Wang; Aizhong Ding (Journal of Environmental Management, 2023)

Graphene induced structure and doping level tuning of evaporated CsPbBr3 on different substrates - Zhaorui Wen; Yunlei Zhong; Bingchen He; Gang Wang; Shengwen Li; Zhen Mu; Jielei Li; Junpeng Xie; Yi Zheng; Guichuan Xing; Guo Hong; Shi Chen (Chemical Engineering Journal, 2023)

Body mass index–based predictions and personalized clinical strategies for colorectal cancer in the context of PPPM - Yun-Jia Gu; Li-Ming Chen; Mu-En Gu; Hong-Xiao Xu; Jing Li; Lu-Yi Wu (EPMA Journal, 2022)
Currently colorectal cancer (CRC) is the third most prevalent cancer worldwide. Body mass index (BMI) is frequently used in CRC screening and risk assessment to quantitatively evaluate weight. However, the impact of BMI on clinical strategies for CRC has received little attention. Within the framework of the predictive, preventive, and personalized medicine (3PM/PPPM), we hypothesized that BMI stratification would affect the primary, secondary, and tertiary care options for CRC and we conducted a critical evidence-based review. BMI dynamically influences CRC outcomes, which helps avoiding adverse treatment effects. The outcome of surgical and radiation treatment is adversely affected by overweight (BMI ≥ 30) or underweight (BMI < 20). A number of interventions, such as enhanced recovery after surgery and robotic surgery, can be applied to CRC at all levels of BMI. BMI-controlling modalities such as exercise, diet control, nutritional therapy, and medications may be potentially beneficial for patients with CRC. Patients with overweight are advised to lose weight through diet, medication, and physical activity while patients suffering of underweight require more focus on nutrition. BMI assists patients with CRC in better managing their weight, which decreases the incidence of adverse prognostic events during treatment. BMI is accessible, noninvasive, and highly predictive of clinical outcomes in CRC. The cost–benefit of the PPPM paradigm in developing countries can be advanced, and the clinical benefit for patients can be improved with the promotion of BMI-based clinical strategy models for CRC.

Prediction of Groundwater Quality Using Seven Types of First-Order Univariate Grey Model in the Chishan Basin, Taiwan - Tzu-Yi Pai; Ray-Shyan Wu; Ching-Ho Chen; Huang-Mu Lo; Terng-Jou Wan; Min-Hsin Liu; Wei-Cheng Chen; Yi-Ping Lin; Chun-Tse Hsu (Water, Air, & Soil Pollution, 2022)

Predation capacity of Bradymonabacteria, a recently discovered group in the order Bradymonadales, isolated from marine sediments - Ya Gong; Xiu-Ya Ping; Chen-Hang Zeng; Shu-Xin Wang; Yi Zhou; Ming-Yi Wang; Da-Shuai Mu; Zong-Jun Du (Archives of Microbiology, 2022)

Xinfangfangia pollutisoli sp. nov., Isolated from Clopyralid-Contaminated Soil - Yang Mu; Jia-Yi Peng; Hui-Ping Wang; Yue Song; Hong-Mei Wang; Qing Chen; Kai Chen (Current Microbiology, 2022)

An Updated Genome Assembly Improves Understanding of the Transcriptional Regulation of Coloration in Midas Cichlid - Yunyun Lv; Yanping Li; Yi Liu; Zhengyong Wen; Yexin Yang; Chuanjie Qin; Qiong Shi; Xidong Mu (Frontiers in Marine Science, 2022)
Midas cichlid ( Amphilophus citrinellus ), a popular aquarium fish, attracts extensive attention from worldwide biologists mainly due to its morphological polymorphism (dark versus gold). Continuous efforts have therefore been paid to address mechanisms of its coloration variants, while it is far away from the detailed illustration of a clear regulatory network. Some limits may come from the absence of a high-quality genome assembly and a relatively accurate gene set. In this study, we sequenced about 149 Gb of nucleotide sequences of Midas cichlid, generating a genome assembly with a total size of 933.5 Mb, which exhibits a good genome continuity with a contig N50 of 10.5 Mb. A total of 25,911 protein-coding genes were annotated and about 90% completeness was achieved, which helps to build a good gene pool for understanding expressional differences of color variation. With the assistance of the final gene set, we identified a total of 277 differential expressional genes (DEGs), of which 97 up- and 180 downregulated were determined in dark-vs-gold comparisons. Two protein-protein interaction (PPI) networks were constructed from these DEGs, and three key functional modules were classified. Hub genes within each module were evaluated, and we found that the third key module contains tyrp1b , oca2 , pmela , tyr , and slc24a5 , which were previously proven to be associated with melanin formation. Two downregulated DEGs ( myl1 and pgam2 ) in the first key module may be involved in muscle movement and spermatogenesis, implying that certain side effects could result from the morphological polymorphism. The first key module, consisting of proteins encoded by upregulated DEGs that were associated with MAPK signaling, Toll-like receptor signaling, and gonadotropin-releasing hormone pathways, may contribute to a negative upstream regulation or downstream influence on melanin biosynthesis. Taken together, our new genome assembly and gene annotation of Midas cichlid provide a high-quality genetic resource for biological studies on this species, and the newly identified key networks and hub genes in dark-vs-gold comparisons enhance our understanding of the transcriptional regulatory mechanisms underlying coloration changes not only in Midas cichlid but also in other fishes from freshwater to marine ecosystems.

Discovery of the non‐cosmopolitan lineages in Candidatus Thermoprofundales - Yi‐Fan Liu; Liu Yang; Zhong‐Lin Liu; Jing Chen; Bo Fang; Lei Zhou; Jin‐Feng Liu; Shi‐Zhong Yang; Ji‐Dong Gu; Bo‐Zhong Mu (Environmental Microbiology, 2022)
Summary The recently proposed order Candidatus Thermoprofundales, currently containing only one family‐level lineage Marine Benthic Group‐D (MBG‐D), is distributed in global subsurface ecosystems and ecologically important, but its diversity, evolution and metabolism remain largely unknown. Here we described two novel family‐level specialized lineages in Ca . Thermoprofundales, JdFR‐43 and HyVt, which are restricted to specific biotopes (primarily in marine hydrothermal vents and occasionally in oil reservoirs and hot springs) in contrast to the cosmopolitan lineage MBG‐D. The comparative genomics revealed that the specialized lineages have streamlined genomes, higher GC contents, enriched genes associated with nucleotide biosynthesis, ribosome biogenesis and DNA repair and additional thermostable aminopeptidases, enabling them to adapt to high‐temperature habitats such as marine hydrothermal vents, deep subsurface oil reservoirs and hot springs. On the contrary, the unique metabolic traits of the cosmopolitan MBG‐D, motility, glycolysis, butanoate metabolism, secondary metabolites production and additional genes for specific peptides and carbohydrates degradation potentially enhance its response to environmental change. Substrate preference is found for most MAGs across all lineages with the ability to utilize both polysaccharides (chitin and starch) and proteinaceous substances, whereas JdFR‐43 members from oil reservoirs can only utilize proteins. These results expand the diversity of C a . Thermoprofundales significantly and further improve our understandings of the adaptations of C a . Thermoprofundales to various environments.

Re-evaluation of the identities of Glossadelphus borneensis and its associated synonyms, G. attenuatus and G. nitidus - Zhao-Qin Yi; Si He; Jun-Jie Wang; Li-Qiang Mu; Yu Jia (Brittonia, 2022)

Associations between species-level indoor microbiome, environmental characteristics, and asthma in junior high schools of Terengganu, Malaysia - Xi Fu; Yi Meng; Yanling Li; Xunhua Zhu; Qianqian Yuan; Aminnuddin Ma’pol; Jamal Hisham Hashim; Zailina Hashim; Gunilla Wieslander; Yi-Wu Zheng; Xu-Xin Lai; Michael Dho Spangfort; et al. (Air Quality, Atmosphere & Health, 2022)

Duplex droplet digital PCR method for the detection of Enterocytozoon hepatopenaei and Vibrio parahaemolyticus acute hepatopancreatic necrosis disease - Huang Zhang; Han‐Yue Gong; Wei‐Wei Cao; Mu‐Yi Que; Lei Ye; Lei Shi (Journal of Fish Diseases, 2022)
Enterocytozoon hepatopenaei (EHP) and Vibrio parahaemolyticus acute hepatopancreatic necrosis disease (VPAHPND) are two of the diseases that have frequently infected farmed shrimp in recent years, causing great economic losses to the shrimp industry worldwide. In this study, we established a sensitive and accurate duplex droplet digital PCR (ddPCR) method that can simultaneously detect and quantify the two pathogens simultaneously. The results showed that the ddPCR methods could detect EHP and VPAHPND specifically. The sensitivity levels of ddPCR for EHP and VPAHPND were 2.3 copies/μl and 4.6 copies/μl, respectively, which were 10‐fold higher than the sensitivity of the qPCR assay and showed good reproducibility. Twenty‐six suspected diseased shrimp samples were used for practical determination. For EHP, the detection rates of ddPCR and qPCR were 53.84% and 42.31%, respectively; for VPAHPND, the detection rates of ddPCR and qPCR were both 23.08%. The results indicated that the ddPCR method shows superiority for detection in samples with low viral loads, which will facilitate monitoring of the source and transmission of EHP and VPAHPND and will help control shrimp epidemic disease.

Tea Polyphenols Improve Down-Regulation of Mitochondrial Functional Gene Expression Induced by Bisphenol A in Zebrafish Ovaries - Xiaoxin Dai; Lijun Qiu; Han Zhang; Chunying Xu; Bo Zhao; Yang Gao; Haidong Li; Yi Mu; Zhangjie Chu (Frontiers in Marine Science, 2022)
The plasticizer bisphenol A, a typical endocrine disrupting chemical, is widely present in the environment. Previous studies demonstrated that exposure to bisphenol A can cause reproductive toxicity, abnormal fertilization, and infertility. However, the mechanisms of low-concentration bisphenol A on the reproductive system and treatment measures have not been fully determined. In this study, we explored the transcriptomic profiles of female zebrafish ovaries. The transcriptomic data revealed that mitochondrial NADH dehydrogenase (mt-Nd) genes were significantly decreased in the bisphenol A-exposed group, while the co-administration of tea polyphenols remarkably elevated the expression of mt-Nd genes. To further explore the expression pattern of the mt-Nd, we analyzed the expression of six mt-Nd genes on different days by qRT-PCR in control, bisphenol A-exposed, and bisphenol A-tea polyphenols ovaries. Here, we found that 0.1 mg/L bisphenol A exposure adversely affects the mitochondrial respiratory chain in ovaries and may lead to reproductive disorders. Finally, our study demonstrated that tea polyphenols play a protective role in ovarian mitochondrial dysfunction in low-concentration bisphenol A-exposed female zebrafish.

A new highly oxygenated germacranolide from Carpesium nepalense var. lanatum (C.B.Clarke) Kitam - Yi-Fan Yu; Yue-Qian Li; Ru-Yue Wang; Xu Liu; Wen-Bo Cui; Xiao-Han Chen; Cheng-Mu Zhao; Feng-Ming Qi; Zhan-Xin Zhang; Dong-Qing Fei (Natural Product Research, 2022)

Composition, Demographic History, and Population Structures of Trichiurus - Kui-Ching Hsu; Mu-Rong Yi; Sui Gu; Xiong-Bo He; Zhi-Sen Luo; Bin Kang; Hung-Du Lin; Yun-Rong Yan (Frontiers in Marine Science, 2022)
Sequences of the complete mitochondrial cytochrome oxidase subunit I gene were used to identify Trichiurus species and examine their population genetic structure and demographic history along the coast of China. Three Trichiurus species were found. Trichiurus japonicus lives in colder waters along the continental shelves in the China Seas, while Trichiurus nanhaiensis lives warmer waters along continental slopes in the South China Sea, and Trichiurus brevis lives in shallow and warmer waters in the South China Sea. The migrations of these species were mainly associated with feeding and spawning preferences. Two major wintering and spawning grounds in the East China Sea and South China Sea were found. All species showed a lack of population genetic structure resulting from their oceanodromous life cycle (the degree of population substructure index N ST = 0.000–0.149), but the results of approximate Bayesian computational approaches suggested population declines or stabilization and differentiation. The results of the T MRCA (time to the most recent common ancestor) showed that during glaciations, the Yellow Sea and the East China Sea were completely exposed, and the South China Sea acted as a refugium. Thus, the populations of these three species experienced differentiation during glaciations. This study also examined the limitations of Bayesian skyline plot analysis.

Overexpression of Cpg15 Alleviates the Oxidative Stress in Neuronal Cells Via Regulating Redox Enzymes and Nrf2 Antioxidative Pathway - Yi Jiang; Jun-Jie Li; Ya-Wei Mu; Han-Yang Jiang; Zi-Xuan Wei; Zi-Yao Xiao; Jing-Jing Zhao; Xian-Hua Chen (Neurotoxicity Research, 2022)

Three-Dimensional Digital Reconstruction of the Cerebellar Cortex: Lobule Thickness, Surface Area Measurements, and Layer Architecture - Junxiao Zheng; Qinzhu Yang; Nikos Makris; Kaibin Huang; Jianwen Liang; Chenfei Ye; Xiaxia Yu; Mu Tian; Ting Ma; Tian Mou; Wenlong Guo; Ron Kikinis; et al. (The Cerebellum, 2022)
The cerebellum is ontogenetically one of the first structures to develop in the central nervous system; nevertheless, it has been only recently reconsidered for its significant neurobiological, functional, and clinical relevance in humans. Thus, it has been a relatively under-studied compared to the cerebrum. Currently, non-invasive imaging modalities can barely reach the necessary resolution to unfold its entire, convoluted surface, while only histological analyses can reveal local information at the micrometer scale. Herein, we used the BigBrain dataset to generate area and point-wise thickness measurements for all layers of the cerebellar cortex and for each lobule in particular. We found that the overall surface area of the cerebellar granular layer (including Purkinje cells) was 1,732 cm 2 and the molecular layer was 1,945 cm 2 . The average thickness of the granular layer is 0.88 mm (± 0.83) and that of the molecular layer is 0.32 mm (± 0.08). The cerebellum (both granular and molecular layers) is thicker at the depth of the sulci and thinner at the crowns of the gyri. Globally, the granular layer is thicker in the lateral-posterior-inferior region than the medial-superior regions. The characterization of individual layers in the cerebellum achieved herein represents a stepping-stone for investigations interrelating structural and functional connectivity with cerebellar architectonics using neuroimaging, which is a matter of considerable relevance in basic and clinical neuroscience. Furthermore, these data provide templates for the construction of cerebellar topographic maps and the precise localization of structural and functional alterations in diseases affecting the cerebellum.

Functional characterization of tyrosine decarboxylase genes that contribute to acteoside biosynthesis in Rehmannia glutinosa - Yan Hui Yang; Mu Rong Yang; Jian Yu Zhu; Ke Wei Dong; Yan Jie Yi; Rui Fang Li; Lei Zeng; Chang Fu Zhang (Planta, 2022)

Delineating the Decussating Dentato-rubro-thalamic Tract and Its Connections in Humans Using Diffusion Spectrum Imaging Techniques - Si-Qi Ou; Peng-Hu Wei; Xiao-Tong Fan; Yi-He Wang; Fei Meng; Mu-Yang Li; Yong-Zhi Shan; Guo-Guang Zhao (The Cerebellum, 2022)

Historical Connectivity and Demography of the Ferocious Reef Crab, Eriphia ferox (Crustacea; Eriphiidae), Demonstrate That Taoyuan Algal Reef Is an Essential Population Source Along the East Taiwan Strait - Mu-Han Chen; Ya-Yi Huang; Bi-Ying Huang; Hernyi Justin Hsieh; Jen Nie Lee; Mei Lin Neo; Hironobu Fukami; Chaolun Allen Chen (Frontiers in Marine Science, 2022)
The east Taiwan Strait is largely fringed by sandy and muddy habitats. However, a massive algal reef made of crustose coralline algae has been found along the coast off Taoyuan city in northwestern Taiwan. The porous structure of Taoyuan Algal Reef harbors high abundance and diversity in marine organisms, including the ferocious reef crab, Eriphia ferox . Such a pivotal geographic location and unique ecological features make Taoyuan Algal Reef a potential stepping stone connecting biotic reefs in the east Taiwan Strait, South China Sea to the south, and even the high latitude of Japan to the north. In this study, we examined the population connectivity and historical demography of E. ferox by analyzing mitochondrial cytochrome oxidase I (COI) fragments of 317 individuals sampled from 21 localities in the northwestern Pacific. Our analyses of haplotype network and pairwise F ST comparisons revealed a lack of phylogeographical structure among E. ferox populations, implying the existence of a migration corridor connecting the South and East China Seas through the east Taiwan Strait. Multiple lines of evidence, including significant values in neutrality tests, unimodally shaped mismatch distributions, and Bayesian skyline plots elucidated the rapid population growth of E. ferox following the sea-level rise after Last Glacial Maximum (ca. 2–10 Ka). Such demographic expansion in E. ferox coincided with the time when Taoyuan Algal Reef started to build up around 7,500 years ago. Coalescent migration analyses further indicated that the large and continuous E. ferox population exclusively found in Datan Algal Reef, the heart of Taoyuan Algal Reef, was a source population exporting migrants both northward and southward to the adjacent populations. The bidirectional gene flow should be attributed to larval dispersal by ocean currents and secondary contact due to historical population expansion. Instead of serving as a stepping stone, our results support that Taoyuan Algal Reef is an essential population source for biotic reef-associated species along the east Taiwan Strait, and highlight the importance of conserving such a unique ecosystem currently threatened by anthropogenic development.

Maternal intake of caffeinated products and birth defects: a systematic review and meta-analysis of observational studies - Yan Yue; Wenxing Li; Jun Tang; Yan Zeng; Tao Xiong; Xia Qiu; Jing Shi; Hua Wang; Bin Xia; Lili Luo; Yi Qu; Dezhi Mu (Critical Reviews in Food Science and Nutrition, 2021)

Temporal stability analysis of soil moisture along a coniferous forest hillslope with subtropical monsoon climate in southwest China - Yu-shi Bai; Mu-xing Liu; Jun Yi; Hai-lin Zhang (Journal of Mountain Science, 2021)

Contributions of climate change and human activities to runoff and sediment discharge reductions in the Jialing River, a main tributary of the upper Yangtze River, China - Yiting Shao; Yi He; Xingmin Mu; Guangju Zhao; Peng Gao; Wenyi Sun (Theoretical and Applied Climatology, 2021)

Characterization of expansin genes and their transcriptional regulation by histone modifications in strawberry - Qin Mu; Xianyang Li; Jianhua Luo; Qinwei Pan; Yi Li; Tingting Gu (Planta, 2021)

Environmental tradeoffs in municipal wastewater treatment plant upgrade: a life cycle perspective - Shuai Shao; Hailin Mu; Arturo A. Keller; Yi Yang; Haochen Hou; Fenglin Yang; Yun Zhang (Environmental Science and Pollution Research, 2021)

Fibroblast Growth Factor 9 Stimulates Neuronal Length Through NF-kB Signaling in Striatal Cell Huntington’s Disease Models - Issa Olakunle Yusuf; Hsiu-Mei Chen; Pei-Hsun Cheng; Chih-Yi Chang; Shaw-Jenq Tsai; Jih-Ing Chuang; Chia-Ching Wu; Bu-Miin Huang; H. Sunny Sun; Chuan-Mu Chen; Shang-Hsun Yang (Molecular Neurobiology, 2021)

Correlation between single-nucleotide polymorphisms and statin-induced myopathy: a mixed-effects model meta-analysis - Qian Xiang; Xiao-Dan Zhang; Guang-Yan Mu; Zhe Wang; Zhi-Yan Liu; Qiu-Fen Xie; Kun Hu; Zhuo Zhang; Ling-Yue Ma; Jie Jiang; Yi-Min Cui (European Journal of Clinical Pharmacology, 2021)

The regulation of the small-conductance calcium-activated potassium current and the mechanisms of sex dimorphism in J wave syndrome - Mu Chen; Yudong Fei; Tai-Zhong Chen; Yi-Gang Li; Peng-Sheng Chen (Pflügers Archiv - European Journal of Physiology, 2021)

NO oxidation performance and kinetics analysis of BaMO3 (M=Mn, Co) perovskite catalysts - Ran Ao; Liping Ma; Zhiying Guo; Jing Yang; Liusen Mu; Jie Yang; Yi Wei (Environmental Science and Pollution Research, 2021)

Use of QSAR and SSD methods on deriving predicted no-effect concentrations in seawater and sediment for ten individual parent- and alkyl-PAHs and a case study on the assessment of their ecological risks from the Dalian Bay, China - Ying Wang; Xing Liu; Yi Cong; Jin Fei; Juying Wang; Dian Zhang; Liang Liu; Jingli Mu; Ziwei Yao (Acta Oceanologica Sinica, 2020)

SARS-CoV-2-encoded nucleocapsid protein acts as a viral suppressor of RNA interference in cells - Jingfang Mu; Jiuyue Xu; Leike Zhang; Ting Shu; Di Wu; Muhan Huang; Yujie Ren; Xufang Li; Qing Geng; Yi Xu; Yang Qiu; Xi Zhou (Science China Life Sciences, 2020)

Correction to: Telomerase reconstitution contributes to resetting of circadian rhythm in fibroblasts - Yi Qu; Meng Mao; Xihong Li; Yanyou Liu; Jianmin Ding; Zhou Jiang; Chaomin Wan; Lin Zhang; Zhengrong Wang; Dezhi Mu (Molecular and Cellular Biochemistry, 2020)

A bacterial polysaccharide biosynthesis-related gene inversely regulates larval settlement and metamorphosis of Mytilus coruscus - Li-Hua Peng; Xiao Liang; Rui-Heng Chang; Jia-Yi Mu; Hui-E Chen; Asami Yoshida; Kiyoshi Osatomi; Jin-Long Yang (Biofouling, 2020)

Pesticide residues in vegetables and risk assessment for consumers in Korea during 2010–2014 - Yun-Jeong Yi; Hyo-Jee Joung; Jin-Young Kum; in-Sook Hwang; Mu Sang Kim (Food Additives & Contaminants: Part A, 2020)

Combined effect of polymorphisms of MTHFR and MTR and arsenic methylation capacity on developmental delay in preschool children in Taiwan - Yu-Mei Hsueh; Ying-Chin Lin; Chi-Jung Chung; Ya-Li Huang; Ru-Lan Hsieh; Pai-Tsang Huang; Mei-Yi Wu; Horng-Sheng Shiue; Ssu-Ning Chien; Chih-Ying Lee; Ming-I. Lin; Shu-Chi Mu; et al. (Archives of Toxicology, 2020)

Biomechanical Comparison of Lumbar Motion Unit Stability Following Posterior Instrumentation with Facet Spacers and Facet Screws - Mu-Yi Liu; Tsung-Ting Tsai; Lih-Huei Chen; Wen-Huang Liang; Po-Liang Lai; Ching-Lung Tai (Journal of Medical and Biological Engineering, 2020)
Purpose Lumbar posterior instrumentation for facet stabilization has become popular for the treatment of lumbar instability. The present study investigated and compared facet stabilization following lumbar posterior instrumentation with facet spacers and facet screws using porcine lumbar spines. Methods Eighteen L5–L6 lumbar motion units (LMUs) of the porcine spines were randomly divided into three groups (un-instrumented, facet-spacer and facet-screw). In the un-instrumented group (control), all ligamentous structures were preserved. In the facet-spacer group, two facet spacers were inserted into the joint spaces of the bilateral upper and lower facets. In the facet-screw group, two cannulated screws were used to transfix the bilateral upper and lower facets. With the use of a material testing machine, a gradually increasing moment of up to 6000 N-mm was generated in flexion, extension, lateral bending and torsion motions to compare facet stabilization among the groups. Results The facet-spacer group was significantly stiffer than the facet-screw group in extension ( p = 0.013), whereas the facet-screw group was significantly stiffer than the facet-spacer group in axial rotation ( p = 0.004). No statistically significant differences were observed between the two fixation techniques in flexion ( p = 0.284) and lateral bending ( p = 0.085). Conclusion Both facet-spacer and facet-screw fixation techniques significantly improve stability in a single LMU. Facet-spacer fixation provided better stabilization in extension, while facet-screw fixation provided better stabilization in axial rotation.

Implementation of the Land Surface Processes into a Vector Vorticity Equation Model (VVM) to Study its Impact on Afternoon Thunderstorms over Complex Topography in Taiwan - Chien-Ming Wu; Hsiao-Chun Lin; Fang-Yi Cheng; Mu-Hua Chien (Asia-Pacific Journal of Atmospheric Sciences, 2019)

Lacustrine carbonates of Paleogene in Zhanhua Sag, Bohai Bay Basin, East China - Shuo Yi; Wenhui Huang; Nana Mu (Carbonates and Evaporites, 2019)

Association of plasma folate, vitamin B12 levels, and arsenic methylation capacity with developmental delay in preschool children in Taiwan - Ying-Chin Lin; Chi-Jung Chung; Ya-Li Huang; Ru-Lan Hsieh; Pai-Tsang Huang; Mei-Yi Wu; Pui-Lam Ao; Horng-Sheng Shiue; Shiau-Rung Huang; Chien-Tien Su; Ming-I Lin; Shu-Chi Mu; et al. (Archives of Toxicology, 2019)

Effects of water content on the shear behavior and critical state of glacial till in Tianmo Gully of Tibet, China - Gordon G. D. Zhou; Lei-lei Chen; Qing-yi Mu; Kahlil Fredrick E. Cui; Dong-ri Song (Journal of Mountain Science, 2019)

Compression characteristics of saturated re-compacted glacial tills in Tianmo Gully of Tibet, China - Lei-lei Chen; Gordon G. D. Zhou; Qing-yi Mu; Kahlil Fredrick E. Cui; Dong-ri Song (Journal of Mountain Science, 2019)

MAOA-VNTR Genotype Effects on Ventral Striatum-Hippocampus Network in Alzheimer’s Disease: Analysis Using Structural Covariance Network and Correlation with Neurobehavior Performance - Hsin-I Chang; Ya-Ting Chang; Shih-Jen Tsai; Chi-Wei Huang; Shih-Wei Hsu; Mu-En Liu; Wen-Neng Chang; Chia-Yi Lien; Shu-Hua Huang; Chen-Chang Lee; Chiung-Chih Chang (Molecular Neurobiology, 2019)

Effects of dietary Allium mongolicum Regel polysaccharide on growth, lipopolysaccharide-induced antioxidant responses and immune responses in Channa argus - Mu-Yang Li; Xin-Ming Zhu; Xiao-Tian Niu; Xiu-Mei Chen; Jia-Xin Tian; Yi-Di Kong; Dong-Ming Zhang; Lei Zhao; Gui-Qin Wang (Molecular Biology Reports, 2019)

Blockade of Endogenous Angiotensin-(1–7) in Hypothalamic Paraventricular Nucleus Attenuates High Salt-Induced Sympathoexcitation and Hypertension - Xiao-Jing Yu; Yu-Wang Miao; Hong-Bao Li; Qing Su; Kai-Li Liu; Li-Yan Fu; Yi-Kang Hou; Xiao-Lian Shi; Ying Li; Jian-Jun Mu; Wen-Sheng Chen; Wei Cui; et al. (Neuroscience Bulletin, 2019)

Base cation concentrations in forest litter and topsoil have different responses to climate and tree species along elevational gradients - Feng Xue; Ming-fei Zhao; Yu-hang Wang; Mu-yi Kang; Kai-xiong Xing; Guo-yi Wang; Jing-jing Shi; Chen Chen; Yuan Jiang (Journal of Mountain Science, 2019)

Association of TRIMCyp and TRIM5α from assam macaques leads to a functional trade-off between HIV-1 and N-MLV inhibition - Dan Mu; Jia-Wu Zhu; Feng-Liang Liu; Hong-Yi Zheng; Yong-Tang Zheng (Science China Life Sciences, 2018)

Molecular surveillance of Vittaforma-like microsporidia by a small-volume procedure in drinking water source in Taiwan: evidence for diverse and emergent pathogens - Jung-Sheng Chen; Bing-Mu Hsu; Hsin-Chi Tsai; Yu-Pin Chen; Tung-Yi Huang; Kuan-Ying Li; Dar-Der Ji; Herng-Sheng Lee (Environmental Science and Pollution Research, 2018)

Ionizing radiation exposure: hazards, prevention, and biomarker screening - Hongxiang Mu; Jing Sun; Linwei Li; Jie Yin; Nan Hu; Weichao Zhao; Dexin Ding; Lan Yi (Environmental Science and Pollution Research, 2018)

Cadmium and lead accumulations and agronomic quality of a newly bred pollution-safe cultivar (PSC) of water spinach - Ying-Ying Huang; Yang-Xiu Mu; Chun-Tao He; Hui-Ling Fu; Xue-Song Wang; Fei-Yue Gong; Zhong-Yi Yang (Environmental Science and Pollution Research, 2018)

Anomalous gray matter structural networks in recent onset post-traumatic stress disorder - Shun Qi; Yun-Feng Mu; Long-Biao Cui; Jian Zhang; Fan Guo; Qing-Rong Tan; Mei Shi; Kang Liu; Yi-Bin Xi; Nan-Yin Zhang; Xiao-Liang Zhang; Yong He; et al. (Brain Imaging and Behavior, 2018)

An Inframe Trinucleotide Deletion in MTRR Exon 1 is Associated with the Risk of Spina Bifida - Jun Zhang; Xiao-lu Dai; Gui-cen Liu; Juan Wang; Xue-yi Ren; Mu-hua Jin; Nan-nan Mi; Shu-qin Wang (NeuroMolecular Medicine, 2017)

First detection of enteric adenoviruses genotype 41 in recreation spring areas of Taiwan - Yi-Jia Shih; Chi-Wei Tao; Hsin-Chi Tsai; Wen-Chien Huang; Tung-Yi Huang; Jung-Sheng Chen; Yi-Chou Chiu; Tsui-Kang Hsu; Bing-Mu Hsu (Environmental Science and Pollution Research, 2017)

Optimization of continuous-flow solid-phase denitrification via coupling carriers in enhancing simultaneous removal of nitrogen and organics for agricultural runoff purification - Yi Lu; Xiaoqing Zhang; Lijuan Feng; Guangfeng Yang; Zhou Zheng; Junzhi Liu; Jun Mu (Biodegradation, 2017)

Human activity and climate variability impacts on sediment discharge and runoff in the Yellow River of China - Yi He; Fei Wang; Xingmin Mu; Lanqin Guo; Peng Gao; Guangju Zhao (Theoretical and Applied Climatology, 2017)

Changes in daily and monthly rainfall in the Middle Yellow River, China - Yi He; Peng Tian; Xingmin Mu; Peng Gao; Guangju Zhao; Fei Wang; Pengfei Li (Theoretical and Applied Climatology, 2017)

A new quinolinone and its natural/artificial derivatives from a shark gill-derived fungus Penicillium polonicum AP2T1 - Yi Zhang; Jun Mu; Frank Essmann; Yan Feng; Markus Kramer; Hai-yan Bao; Stephanie Grond (Natural Product Research, 2017)

Erratum to: Diurnal and seasonal variation of the elevation gradient of air temperature in the northern flank of the western Qinling Mountain range, China - Guo-yi Wang; Ming-fei Zhao; Mu-yi Kang; Kai-xiong Xing; Yu-hang Wang; Feng Xue; Chen Chen (Journal of Mountain Science, 2017)

Diurnal and seasonal variation of the elevation gradient of air temperature in the northern flank of the western Qinling Mountain range, China - Guo-yi Wang; Ming-fei Zhao; Mu-yi Kang; Kai-xiong Xing; Yu-hang Wang; Feng Xue; Chen Chen (Journal of Mountain Science, 2017)

Rapid Fabrication of a Cell-Seeded Collagen Gel-Based Tubular Construct that Withstands Arterial Pressure - Ho-Yi Tuan-Mu; Po-Ching Lu; Pei-Yuan Lee; Chien-Chih Lin; Chun-Jung Chen; Lynn L.H. Huang; Jia-Horng Lin; Jin-Jia Hu (Annals of Biomedical Engineering, 2016)

Antidepressant-like effects of standardized gypenosides: involvement of brain-derived neurotrophic factor signaling in hippocampus - Rong-Hao Mu; Xiao-Yan Fang; Shuang-Shuang Wang; Cheng-Fu Li; Shao-Mei Chen; Xue-Mei Chen; Qing Liu; Yu-Cheng Li; Li-Tao Yi (Psychopharmacology, 2016)

The effects of CYP1A inhibition on alkyl-phenanthrene metabolism and embryotoxicity in marine medaka (Oryzias melastigma) - Jingli Mu; Fei Jin; Juying Wang; Ying Wang; Yi Cong (Environmental Science and Pollution Research, 2016)

Sourcing copper ores for production of bronzes excavated at Shuangyantang, a Western Zhou (1046–771 bc) site in Chongqing (Southwest China): evidence from lead isotope analysis - Xiaopan Fan; Di Mu; Jun Yi; Hongmin Wang; Wugan Luo (Archaeological and Anthropological Sciences, 2016)

SPECT Imaging of 2-D and 3-D Distributed Sources with Near-Field Coded Aperture Collimation: Computer Simulation and Real Data Validation - Zhiping Mu; Lawrence W. Dobrucki; Yi-Hwa Liu (Journal of Medical and Biological Engineering, 2016)

Parasite and Infected-Erythrocyte Image Segmentation in Stained Blood Smears - Yi-Wen Hung; Ching-Lin Wang; Chuin-Mu Wang; Yung-Kuan Chan; Lin-Yu Tseng; Chiu-Wen Lee; Kwong-Chung Tung (Journal of Medical and Biological Engineering, 2015)

Prevalence, quantification, and typing of human adenoviruses detected in river water in Taiwan - Zhon-Min Huang; Bing-Mu Hsu; Po-Min Kao; Tien-Yu Chang; Tsui-Kang Hsu; Ying-Ning Ho; Yi-Chun Yang; Yu-Li Huang (Environmental Science and Pollution Research, 2015)

Antibiotic resistance pattern and gene expression of non-typhoid Salmonella in riversheds - Chao-Yu Hsu; Bing-Mu Hsu; Wen-Tsai Ji; Jung-Sheng Chen; Tsui-Kang Hsu; Dar-Der Ji; Shao-Feng Tseng; Yi-Chou Chiu; Po-Min Kao; Yu-Li Huang (Environmental Science and Pollution Research, 2015)

Occurrence of sulfonamide-, tetracycline-, plasmid-mediated quinolone- and macrolide-resistance genes in livestock feedlots in Northern China - Quanhua Mu; Jin Li; Yingxue Sun; Daqing Mao; Qing Wang; Yi Luo (Environmental Science and Pollution Research, 2015)

Occurrence and distribution of sulfonamides, tetracyclines, quinolones, macrolides, and nitrofurans in livestock manure and amended soils of Northern China - Jie Hou; Weining Wan; Daqing Mao; Chong Wang; Quanhua Mu; Songyan Qin; Yi Luo (Environmental Science and Pollution Research, 2015)

Detection of inherited mutations for hereditary cancer using target enrichment and next generation sequencing - Yanfang Guan; Hong Hu; Yin Peng; Yuhua Gong; Yuting Yi; Libin Shao; Tengfei Liu; Gairui Li; Rongjiao Wang; Pingping Dai; Yves-Jean Bignon; Zhe Xiao; et al. (Familial Cancer, 2015)

8-Oxo-7,8-dihydroguanine and 8-oxo-7,8-dihydro-2′-deoxyguanosine concentrations in various human body fluids: implications for their measurement and interpretation - Chiung-Wen Hu; Marcus S. Cooke; Yi-Hung Tsai; Mu-Rong Chao (Archives of Toxicology, 2015)

Probabilistic ecological risk assessment of cadmium in the Bohai Sea using native saltwater species - Jingli Mu; Juying Wang; Ying Wang; Yi Cong; Zhifeng Zhang (Acta Oceanologica Sinica, 2014)

Characterization of the mitochondrial genome and phylogeny of the black arowana (Osteoglossum ferreirai) - Xidong Mu; Yi Liu; Xuejie Wang; Chao Liu; Hongmei Song; Yinchang Hu; Jianren Luo (Biologia, 2014)

Prognostic significance of TBX2 expression in non-small cell lung cancer - Bo Hu; Hai-Ping Mu; Yu-Qing Zhang; Chong-Yi Su; Jian-Tao Song; Chong Meng; Dong-Xing Liu (Journal of Molecular Histology, 2014)

On the Decellularization of Fresh or Frozen Human Umbilical Arteries: Implications for Small-Diameter Tissue Engineered Vascular Grafts - Ho-Yi Tuan-Mu; Chen-Hsiang Yu; Jin-Jia Hu (Annals of Biomedical Engineering, 2014)

Four chlorinated depsidones from a seaweed-derived strain of Aspergillus unguis and their new biological activities - Yi Zhang; Jun Mu; Yan Feng; Lixue Wen; Jinyuan Han (Natural Product Research, 2014)

Pyramiding of Bt cry1Ia8 and cry1Ba3 genes into cabbage (Brassica oleracea L. var. capitata) confers effective control against diamondback moth - Dengxia Yi; Lei Cui; Li Wang; Yumei Liu; Mu Zhuang; Yangyong Zhang; Jie Zhang; Zhihong Lang; Zhenxian Zhang; Zhiyuan Fang; Limei Yang (Plant Cell, Tissue and Organ Culture (PCTOC), 2013)

Whole exome sequencing identifies mutation of EDNRA involved in ACTH-independent macronodular adrenal hyperplasia - Jie Zhu; Liang Cui; Wei Wang; Xing-Yi Hang; A-Xiang Xu; Su-Xia Yang; Jing-Tao Dou; Yi-Ming Mu; Xu Zhang; Jiang-Ping Gao (Familial Cancer, 2013)

Reduced lung cancer incidence attributable to decreased tobacco use in urban Shanghai - Mu Hu; Youxin Wang; Yi Zhang; Xiuyi Zhi (Cancer Causes & Control, 2013)

Identification and quantitative detection of Legionella spp. in various aquatic environments by real-time PCR assay - Po-Min Kao; Min-Che Tung; Bing-Mu Hsu; Yi-Chou Chiu; Cheng-Yu She; Shu-Min Shen; Yu-Li Huang; Wen-Chien Huang (Environmental Science and Pollution Research, 2013)

Synthesis of novel isoquinolinone and 1,2-dihydroisoquinoline scaffolds via Ugi reaction and ring opening reaction of furans - Fei Ji; Wen-bin Yi; Mu Sun; Mei-fang Lv; Chun Cai (Molecular Diversity, 2013)

An Arabidopsis mutant atcsr-2 exhibits high cadmium stress sensitivity involved in the restriction of H2S emission - Ya-wei Li; Ze-hua Gong; Yao Mu; Yi-xian Zhang; Zeng-jie Qiao; Li-ping Zhang; Zhu-ping Jin; Hua Li; Yan-xi Pei (Journal of Zhejiang University-SCIENCE B, 2012)

Integrin β8 Signaling in Neonatal Hypoxic–Ischemic Brain Injury - Li Zhang; Yi Qu; Binzhi Tang; Fengyan Zhao; Tao Xiong; Donna Ferriero; Dezhi Mu (Neurotoxicity Research, 2012)

Occurrence of diarrheagenic Escherichia coli genes in raw water of water treatment plants - Shih-Wei Huang; Bing-Mu Hsu; Yen-Jui Su; Dar-Der Ji; Wei-Chen Lin; Jyh-Larng Chen; Feng-Cheng Shih; Po-Min Kao; Yi-Chou Chiu (Environmental Science and Pollution Research, 2012)

Genetic variant in TP63 on locus 3q28 is associated with risk of lung adenocarcinoma among never-smoking females in Asia - H. Dean Hosgood; Wen-Chang Wang; Yun-Chul Hong; Jiu-Cun Wang; Kexin Chen; I-Shou Chang; Chien-Jen Chen; Daru Lu; Zhihua Yin; Chen Wu; Wei Zheng; Biyun Qian; et al. (Human Genetics, 2012)

Molecular detection and comparison of Acanthamoeba genotypes in different functions of watersheds in Taiwan - Po-Min Kao; Bing-Mu Hsu; Nai-Hsiung Chen; Kuan-Hao Huang; Chin-Chun Huang; Dar-Der Ji; Jung-Sheng Chen; Wei-Chen Lin; Shih-Wei Huang; Yi-Chou Chiu (Environmental Monitoring and Assessment, 2012)

Increased prevalence of seizures in boys who were probands with the FMR1 premutation and co-morbid autism spectrum disorder - Weerasak Chonchaiya; Jacky Au; Andrea Schneider; David Hessl; Susan W. Harris; Meredith Laird; Yi Mu; Flora Tassone; Danh V. Nguyen; Randi J. Hagerman (Human Genetics, 2012)

Sucrose treatment alters floral induction and development in vitro in gloxinia - Ming-Zhe Zhang; Li-Ling Wang; Dan Ye; Xi Chen; Zhi-Yi Wu; Xiao-Jia Lin; Wu-Jian Chen; Hong-Wu Bian; Ning Han; Mu-Yuan Zhu (In Vitro Cellular & Developmental Biology - Plant, 2012)

Positive allelopathic stimulation and underlying molecular mechanism of achyranthe under continuous monoculture - Zhen-Fang Li; Zi-Guan Zhang; Dong-Feng Xie; Lin-Quan Dai; Lan-Fang Zhu; Ji Li; Zong-Quan Liu; Yan-Qiu Yang; Lin-Kun Wu; Mu-Ji Huang; Zhong-Yi Zhang; Wen-Xiong Lin (Acta Physiologiae Plantarum, 2011)

Lactoferrin: an iron-binding antimicrobial protein against Escherichia coli infection - Chih-Ching Yen; Chih-Jie Shen; Wu-Huei Hsu; Yi-Hsin Chang; Hsin-Tang Lin; Hsiao-Ling Chen; Chuan-Mu Chen (BioMetals, 2011)

Using Seven Types of GM (1, 1) Model to Forecast Hourly Particulate Matter Concentration in Banciao City of Taiwan - Tzu-Yi Pai; Ching-Lin Ho; Shyh-Wei Chen; Huang-Mu Lo; Pao-Jui Sung; Shu-Wen Lin; Wei-Jia Lai; Shih-Chi Tseng; Shu-Ping Ciou; Jui-Ling Kuo; Jing-Tang Kao (Water, Air, & Soil Pollution, 2011)

Correlation between pigmentation and larval settlement deterrence by Pseudoalteromonas sp. sf57 - Yi-Li Huang; Mu Li; Zhiliang Yu; Pei-Yuan Qian (Biofouling, 2011)

Alternative splicing of the antitrypsin gene in the silkworm, Bombyx mori - Hui-fen Liu; Yi-nü Li; Ru Jia; Wei-zheng Cui; Zhi-mei Mu; Zhi-fang Zhang (Molecular Biology Reports, 2011)

Porcine lactoferrin as feedstuff additive elevates avian immunity and potentiates vaccination - Che-Ming Hung; Shinn-Chih Wu; Chih-Ching Yen; Ming-Fong Lin; Yi-Wen Lai; Yu-Tang Tung; Hsiao-Ling Chen; Chuan-Mu Chen (BioMetals, 2010)

Probiotic Lactobacillus casei Expressing Human Lactoferrin Elevates Antibacterial Activity in the Gastrointestinal Tract - Hsiao-Ling Chen; Yi-Wen Lai; Chua-Shun Chen; Te-Wei Chu; Willie Lin; Chih-Ching Yen; Ming-Fong Lin; Ming-Yu Tu; Chuan-Mu Chen (BioMetals, 2010)

The Role of Integrin αvβ8 in Neonatal Hypoxic-Ischemic Brain Injury - Jinhui Li; Yi Qu; Xihong Li; Deyuan Li; Fengyan Zhao; Meng Mao; Donna Ferriero; Dezhi Mu (Neurotoxicity Research, 2010)

Lipopolysaccharide upregulates uPA, MMP-2 and MMP-9 via ERK1/2 signaling in H9c2 cardiomyoblast cells - Yi-Chang Cheng; Li-Mien Chen; Mu-Hsin Chang; Wei-Kung Chen; Fuu-Jen Tsai; Chang-Hai Tsai; Tung-Yuan Lai; Wei-Wen Kuo; Chih-Yang Huang; Chung-Jung Liu (Molecular and Cellular Biochemistry, 2009)

The effect of combination treatment with docosahexaenoic acid and 5-fluorouracil on the mRNA expression of apoptosis-related genes, including the novel gene BCL2L12, in gastric cancer cells - Zhihong Zhuo; Leming Zhang; Qitian Mu; Yanru Lou; Zhaohui Gong; Yijiu Shi; Guifang Ouyang; Yi Zhang (In Vitro Cellular & Developmental Biology - Animal, 2009)

Localization of QTL for basal root thickness in japonica rice and effect of marker-assisted selection for a major QTL - Lifeng Liu; Ping Mu; Xueqin Li; Yanying Qu; Yi Wang; Zichao Li (Euphytica, 2008)

Variants of Lipopeptides Produced by Bacillus licheniformis HSN221 in Different Medium Components Evaluated by a Rapid Method ESI-MS - Yi-Ming Li; Namir I. A. Haddad; Shi-Zhong Yang; Bo-Zhong Mu (International Journal of Peptide Research and Therapeutics, 2008)

Telomerase reconstitution contributes to resetting of circadian rhythm in fibroblasts - Yi Qu; Meng Mao; Xihong Li; Yanyou Liu; Jianmin Ding; Zhou Jiang; Chaomin Wan; Lin Zhang; Zhengrong Wang; Dezhi Mu (Molecular and Cellular Biochemistry, 2008)

Enhanced migration and CXCR4 over-expression in fibroblasts with telomerase reconstitution - Yi Qu; Meng Mao; Xihong Li; Lin Zhang; Xiang Huang; Chunlei Yang; Fengyang Zhao; Ying Xiong; Dezhi Mu (Molecular and Cellular Biochemistry, 2008)

Methylenetetrahydrofolate reductase (MTHFR) C677T and A1298C polymorphisms and the risk of primary Hepatocellular Carcinoma (HCC) in a Chinese population - Li-Na Mu; Wei Cao; Zuo-Feng Zhang; Lin Cai; Qing-Wu Jiang; Nai-Chieh You; Binh Yang Goldstein; Guo-Rong Wei; Chuan-Wei Chen; Qing-Yi Lu; Xue-Fu Zhou; Bao-Guo Ding; et al. (Cancer Causes & Control, 2007)

Antifungal agent and other constituents from Cynanchum otophyllum - Yi-Bin Zhao; Yue-Mao Shen; Hong-Ping He; Quan-Zhang Mu; Xiao-Jiang Hao (Natural Product Research, 2007)

A rice gene activation/knockout mutant resource for high throughput functional genomics - Yue-Ie Hsing; Chyr-Guan Chern; Ming-Jen Fan; Po-Chang Lu; Ku-Ting Chen; Shuen-Fang Lo; Peng-Kai Sun; Shin-Lon Ho; Kuo-Wei Lee; Yi-Chieh Wang; Wen-Lii Huang; Swee-Suak Ko; et al. (Plant Molecular Biology, 2007)